An Approximate Algebraic Model for Conversion and Light-off Curves by First-order Reactions in Monolith Converters Operated in the Graetz Regime - Martin Wörner (Emission Control Science and Technology, 2026)
The interaction of mass transfer with irreversible first order heterogeneous-homogeneous chemical reactions in an isothermal circular channel with laminar Poiseuille velocity profile is investigated theoretically. Starting from a novel approximate solution for the reactant mass balance valid in the Graetz regime with fully developed concentration field, a one-term exponential model for conversion is derived which depends on three dimensionless groups: the normalized transversal diffusion time scale ( $$α$$ ) and the Damköhler numbers of the heterogeneous ( $${Da}_{\text{w}}>0$$ ) and homogeneous ( $${Da}_{\text{b}}\ge\:0$$ ) reactions. The model requires the determination of the root of a polynomial of the Damköhler numbers, which entails only minimal numerical effort. The accuracy of the model is tested for the case of a heterogeneous reaction ( $${Da}_{\text{b}}=0$$ ), showing good agreement with numerical solutions and formal analytical limits provided $$α\le1$$ . The proposed single channel conversion model is used to determine observed and intrinsic rate constants, as well as kinetic parameters (pre-exponential factor and activation energy), based on literature data regarding NO conversion via selective catalytic reduction in monolith reactors. In combination with temperature dependent rate constant and diffusion coefficient, the model allows studying effects of parameter variations on the light-off curve in monolith reactors within seconds. The proposed model may therefore be a useful tool for engineering design and optimization of monolith converters.

Prediction of Transient NOx Emission from Heavy-Duty Diesel Engine Based on a Novel Model Combining CNN-GRU-KAN Algorithm and Bayesian Optimization Method - Jianxiong Liao; Haojin Wang; Xiaole He; Rongxue Cao; Zhiqiang Han; Jia Fang; Yunlong Tian; Lingwei Meng (Emission Control Science and Technology, 2026)

Understanding Contributions to Particulate Filter Backpressure Using an Analytic Model - Timothy C. Watling (Emission Control Science and Technology, 2026)

Pollutant Adaptive Forecasting of India’s Greenhouse Gas and Air Pollutant Emissions Using Bayesian Dynamic Regression and Conformal Prediction - Ravikiran Chintalapudi; Dadhu Venkata Raghunatha Reddy; Gangadhara Rao Ponugoti; Lodd Battu Bharath Raju; Sunanda A.; Saritha P.; Bahiru Bewket Mitikie (Emission Control Science and Technology, 2026)
Reliable multi-pollutant emission forecasts are needed to coordinate climate mitigation and air quality management. This study developed a Pollutant Adaptive Bayesian Dynamic Regression and Conformal Prediction framework (PA-BDR-CP-X) for India’s methane (CH 4 ), carbon dioxide (CO 2 ), nitrous oxide (N 2 O), oxides of nitrogen (NO x ) and particulate matter 2.5 micrometers (PM 2.5 ) emissions using annual EDGAR emissions, version EDGAR_2025_GHG, and socioeconomic, energy and agricultural covariates for 1970–2024. Its contribution is a workflow that selects a forecasting structure separately for each pollutant from trend-only or covariate augmented Bayesian dynamic regression, autoregressive integrated moving average (ARIMA) and exponential smoothing (ETS), and then applies conformal uncertainty calibration. Models were assessed using a fixed 2020–2024 test and 90 expanding window rolling origin forecasts per pollutant. In the fixed test, covariate augmented PA-BDR-CP-X reduced root mean square error (RMSE) relative to the best ARIMA/ETS benchmark by 35.07% for CH 4 and 18.56% for PM 2.5 . Rolling origin validation selected trend-only PA-BDR-CP-X for CH 4 and PM 2.5 , ARIMA for CO 2 and N 2 O, and ETS for NO x , demonstrating why no single model family should be imposed across pollutants. After full sample refitting, projected increases from 2025 to 2035 ranged from 12.34% for CH 4 to 37.96% for CO 2 . The 95% conformal intervals covered all 35 rolling origin evaluation forecasts per pollutant, but their width indicates conservative uncertainty bounds rather than precise or guaranteed future coverage. The forecasts provide statistical baselines for coal and energy transition planning, fertilizer and nitrogen use management, methane control in livestock, rice and waste systems, and combustion-emission controls for NO x and PM 2.5 .

A Framework Based on Transformer for Carbon Emission Forecasting and Differentiated Decision Support - Suli Cheng; Xuanlong Lu; Jie Li (Emission Control Science and Technology, 2026)

Effect of Equivalence Ratio in a Waste Oil Burner on Performance and Emission Characteristics Fuelled with Sludge Palm Oil Blends - Muhammad Ahmar Zuber; Wira Jazair Yahya; Sonachalam Muthuswamy; Ili Fatimah Abd Razak; Mohamed Shukri Mohamed Ismail; Hirofumi Noge (Emission Control Science and Technology, 2026)

Novel Multivariate Experimental Data Algorithm for Water-Air Ratio Optimization of an Indirect Water Injected Automobile Diesel Engine - Asad Asghar Janjua; Samiur Rahman Shah; Xavier Tauzia (Emission Control Science and Technology, 2026)

Adaptation of NMOG Calculation for Cold Start Tests Performed on Motor Dynamometer - Flavio Bernardes Couto Moreira; Rafael Lúcio Nascimento Silva; Julia Souto de Souza Rodrigues; Raquel Ianine Lima de Souza; Andressa Castro Vilas Boas Louback; Júlio Cézar de Alvarenga Pires; Thiago Werner Louback; Kamilla de Lima Ribeiro Palhares; Remo Dias Bahia de Carvalho; Iolanda de Lourdes Gonçalves Dias (Emission Control Science and Technology, 2026)

A Machine Learning Approach to Performance–Emission Analysis in Dual-Fuel Internal Combustion Engines - Güven Demirtaş; Hakan Yurtkuran; Feyyaz Alpsalaz; Hasan Uzel (Emission Control Science and Technology, 2026)

Optimizing Control Parameters in Multi-Cylinder Engines with Alcohol-Gasoline Blends: Taguchi Approach - Ravindra Sadashiv Deshpande (Emission Control Science and Technology, 2026)

Time-Resolved Dynamics During the Initial Decline in Catalytic Activity of the CO + NO Reaction over Platinum – Elucidating the Role of NCO - Thomas Häber; Samuel Struzek; Lachlan Caulfield; Sui Wan; Florian Maurer; Patrick Lott; Alexei Nefedov; Christof Wöll; Jan-Dierk Grunwaldt; Olaf Deutschmann (Emission Control Science and Technology, 2026)
The reduction of NO by CO over a powdered $${\text {Pt/Al}_{2}}\text {O}_3$$ catalyst in flow reactors is investigated as a function of temperature and stoichiometry at low concentrations typical for emission control. The study investigates the initial decline in conversion over pre-reduced catalysts and its correlation with the formation (and decomposition) of isocyanate (–NCO) on the support, tracked by time-resolved operando and in situ diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS). Free sites on noble metal particles are necessary for both isocyanate formation and decomposition. CO adsorption and isocyanate formation occur on different time scales, but the amount of isocyanate equilibrates with CO coverage. In the presence of hydrogen, isocyanate decomposes rapidly, producing $$\text {NH}_{3}$$ . The timescales for -NCO formation and activity decline are similar, suggesting a direct link or influence by a common process. Findings align with models that show a) isocyanate formation might aid NO dissociation by countering the inhibiting effect of CO adsorption, and/or b) changes in the oxidation state affect both catalytic activity and isocyanate formation.

Effects of Asymmetric Channel Structure on the DPF Capture Performance in Plateau Environment - Jianbin Luo; Xiaojia Liang; Haiguo Zhang; Xiguang Liang; Tianqiang Liu; Bin Ma; Chunmei Jiang (Emission Control Science and Technology, 2026)

Optimization of VCR Diesel Engine Performance, Emission and Combustion Parameters Using Response Surface Methodology employing Azolla Biodiesel With Additives - Nikunj Upadhyay; Randip Kumar Das; Subrata Kumar Ghosh (Emission Control Science and Technology, 2026)

NOx Mitigation via Direct Water Injection in Hydrogen Spark-Ignition Engines - Hassina Ghodbane; Fouad Khaldi; Fethi Bouras (Emission Control Science and Technology, 2026)

Modeling of the GHG Reduction Potential of NH3 Dual-fuel Engines with Tailored Exhaust Gas Aftertreatment - Georgia Voniati; Athanasios Dimaratos; Grigorios Koltsakis; Leonidas Ntziachristos (Emission Control Science and Technology, 2026)
The decarbonization of maritime transport necessitates the adoption of carbon-free fuels, with ammonia (NH₃) emerging as a promising candidate. However, its incomplete combustion, resulting in unburnt NH 3 , and the formation of nitrogen oxides (NOₓ) and nitrous oxide (N₂O), a potent greenhouse gas (GHG), pose significant challenges for emission control. To address these challenges, experimental kinetic data of Fe-BEA, Co-based, and Pt-based catalysts are incorporated into physico-chemical models. Model validation against the experimental data confirms the accurate prediction of NH₃, NOₓ, and N₂O conversion trends. The model is subsequently employed to design and optimize the Exhaust Aftertreatment System (EATS) layouts, including Selective Catalytic Reduction (SCR), SCR with Ammonia Slip Catalyst (ASC), and hybrid Co–Pt ASC configurations, across a range of engine-out NH₃/NOₓ ratios and combustion efficiencies. The results demonstrate that while NOₓ and NH₃ emissions can be effectively mitigated, N₂O formation in ASC-equipped systems constrains total GHG reduction to approximately 76% compared to conventional diesel operation. A hybrid ASC configuration combining Co and Pt catalysts successfully reduced N₂O selectivity, achieving up to 50% additional GHG reduction.

Advanced Combustion Design with Coupled Unit Operations for Flowsheet Development using DETCHEM and Machine Learning Tools - Eric A. Daymo; Anna Lee Tonkovich (Emission Control Science and Technology, 2026)

Process-Oriented Modeling of Urea-Water Solution as a Multi-Component Fluid with the Aid of Apparent Properties for CFD Spray Applications - Giuliano Andrea Ercolano; Toni Dageförde; Nico Jurtz; Matthias Kraume (Emission Control Science and Technology, 2026)

Measurement Systems and Characterization of Brake Wear Particles: A Literature Review - Marie Hoff; Yan-Ming Chen; Christophe Bressot; Martin Morgeneyer (Emission Control Science and Technology, 2026)

Toward Automated Catalyst Preparation of Monolithic Honeycombs for Ammonia Oxidation by Robot-Controlled Washcoating - Tim Delrieux; Maya Eyleen Ludwig; Joachim Czechowsky; Paolo Dolcet; Florian Maurer; Maria Casapu; Jan-Dierk Grunwaldt (Emission Control Science and Technology, 2026)

Comparison of Single-Tower and Two-Tower Processes for Absorption of Carbon Dioxide From Marine Engine Exhaust - Chen-Chih Hung; Ming-Wen Yang; Van Dai Hai Truong; Jeffrey D. Ward (Emission Control Science and Technology, 2026)

Information Leakage Prevention and Multi-Scale Feature Modeling for Carbon Emission Time Series Forecasting - Heping Wang; Junxuan Yao (Emission Control Science and Technology, 2026)

Effectiveness of Motorcycle Idle-Stop Systems in Mitigating Real-World Tailpipe Emissions of Air Pollutants - Narayan Babu Dhital; Hsi-Hsien Yang; Te-Jui Hsieh; Hsiang-Wei Chen; Shang-Wei Huang (Emission Control Science and Technology, 2026)

Evolution of Maritime CO₂ Performance Under the EU MRV Framework (2018–2023): Emission Patterns and a Baseline for Policy Assessment - Oumaima Bouanani; Sara Sandabad; Hassan Mabchour; Moulay El Houssine Ech-Chhibat (Emission Control Science and Technology, 2026)

Impact of DTBP on Performance and Emission Characteristics of Engines Fueled with Gasoline-Ethanol Blends - Rajeeb Kumar Upadhyay; Kirti Bhushan Mishra (Emission Control Science and Technology, 2026)

Spray Characterization and CFD Simulation Workflow Analysis of Industrial Air-assist Nozzles in the Field of SCR Application - Giuliano A. Ercolano; Toni Dageförde; Mona Al-Mqbas; Nico Jurtz; Friedrich Dinkelacker; Matthias Kraume (Emission Control Science and Technology, 2026)

Performance and Emission Evaluation of a CRDI Diesel Engine Fueled with Algae Biodiesel and Hydrogen Enrichment - Debarup Borah; Rahul Dev Misra (Emission Control Science and Technology, 2026)

Influence of Combustion Strategy and Fuel Ethanol Content on Effective Density, Concentration, and Size of Particles Emitted by a Lean Burn Gasoline Direct Injection Engine - Weiqi Chen; Noah Bock; William Northrop; David Kittelson (Emission Control Science and Technology, 2025)
Particle number, size, and mass concentration; effective density; and mass-mobility coefficient are measured for a gasoline direct injection (GDI) engine fueled with E10, E30, and E50 ethanol blends and operated in three combustion modes: Stoichiometric; Lean Homogeneous; and Lean Stratified. The focus of this study is on solid particles, so all measurements are made behind a catalytic stripper. Two configurations for measuring effective density are compared: DMA-CPMA-CPC and CPMA-SMPS. Our measurements show no difference between densities measured with DMA-CPMA-CPC and CPMA-SMPS configurations within experimental uncertainty. Both combustion mode and ethanol concentration strongly influence particle emissions. Using E10: Stoichiometric operation produces the lowest particle number concentration and highest effective density; Lean Homogeneous gives the lowest particle volume and mass, smallest particles, and lowest effective density; Lean Stratified produces the highest particle concentrations and effective densities. Increasing ethanol content under Stoichiometric and Lean Stratified conditions decreases number and mass concentrations with only small changes in density; but under Lean Homogeneous conditions increases mass and number concentrations and significantly increases density. Using the measured effective densities and particle size distributions measured with a TSI EEPS, solid particle mass is calculated using the integrated particle size distribution (IPSD) method and compared to black carbon mass (BC) measured with a Micro Soot Sensor (MSS). In most cases, the IPSD method gives higher mass concentrations than the MSS BC concentrations. This is consistent with the presence of non-light absorbing material – likely ash and tightly bound hydrocarbons – not detected by the MSS. However, errors in measurement of the upper end of the EEPS size distribution, where most of the mass is found, may play a role.

EVCBiLNet: Carbon Emission forecasting Model Based on CNN-BiLSTM and Secondary Feature Decomposition - Shuo Feng; Yu Gu; Yanyan Zhao; Lei Chen; Xu Tang; Xinkai Qiao; Danli Wang (Emission Control Science and Technology, 2025)

Experimental Evaluation of Multi-Ferrite Nanoparticles-Doped Tamarindus indica Biodiesel in a CI Engine: Performance, Combustion, and Emission Analysis - Kannam Sree Sruthi; Sathya Vara Prasad Lankapalli; Jaikumar Sagari (Emission Control Science and Technology, 2025)

Effect on Performance, Combustion and Emission Characteristics of Spark Ignition Engine Powered by Premium Level Gasohol-Paraffin Blends with Spark Advancement and Spark Retardment - Sujit Kumbhar; Sanjay Khot (Emission Control Science and Technology, 2025)

V2O5-TiO2 SCR Plate Catalysts for High Dust De-NOx Applications: A Comprehensive Characterization Study - S. Rajath; Muzammil Bagewadi; N. D. Shivakumar (Emission Control Science and Technology, 2025)

Influence of 2-EHN and DTBP on Diesel Engine Performance and Emissions Using Tire Pyrolysis Oil - Rajeev Singh Chauhan; Nitin Shrivastava; Veerendra Kumar (Emission Control Science and Technology, 2025)

Innovation and CO2 Emissions Nexus in the Top Ten Innovative Countries: The Role of Economic Growth and Disaggregated Energy Consumption - Md. Saiful Islam; Sk Habibur Rahaman (Emission Control Science and Technology, 2025)

Influence of Injection Timing on the Combustion of Adding Metal-Water Additives into Diesel Fuel - Esmail Khalife (Emission Control Science and Technology, 2025)

Utilisation of Ethanol for Efficiency Improvement and Emissions Reduction in an Automotive Spark Ignition Engine with Oxygen-Enriched Air - Nidhi (Emission Control Science and Technology, 2025)

Emission Profiles of Airborne Particulate Size-Segregated Carbonaceous Fractions of Stationary Diesel Engine and Impact Assessment of their Depositions in Human Lungs - Vishnu Kumar; Sailesh N. Behera; ‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬Mudit Yadav; Jun He; Susant K. Padhi; Bikash R. Parida; Mukesh Sharma; Rajasekhar Balasubramanian‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬ (Emission Control Science and Technology, 2025)

SiC Sponge Potentially Applied to PM Filter for Gasoline Soot - Kazuhiro Yamamoto; Maho Hirota; Yuko Inui (Emission Control Science and Technology, 2025)

Efficient Electrode Configuration for NOX Treatment from Diesel Engine Exhaust at Low Applied Voltage - Sarbesh Bhattacherjee; Sankarsan Mohapatro (Emission Control Science and Technology, 2025)

Enhanced Abatement of Hydrocarbons Using Iron Tailings/Foundry Sand Activated Through Plasma Catalysis of Diesel Exhaust - Sakshi Vijay; B. S. Rajanikanth (Emission Control Science and Technology, 2025)

Replacing Coal with Ammonia Gas in Ferronickel Production: A Comparison from an Environmental and Economic Point of View - Sungging Pintowantoro; Retno Widyaningrum; Chandra Aryo Wibowo; Yuli Setiyorini; Fahny Ardian; Muhammad Bagas Ananda; Fakhreza Abdul (Emission Control Science and Technology, 2025)

Influence of Engine Mileage on Emissions of an Aged Retrofitted Spark Ignition Engine Fueled with Gasoline and Compressed Natural Gas - Michael J. Kyando; Justin W. Ntalikwa; Thomas Kivevele (Emission Control Science and Technology, 2025)

Real-Time Prediction and Control of NOx Emissions in Heavy-Duty Diesel Vehicles Using OBD Data and Deep Learning Models - Tao Li; Xin Lou; Baoli Gong; Guoquan Xie; Kui Wang; Honghao Zhang; Yong Peng (Emission Control Science and Technology, 2025)

Two Simulated Bench Driving Cycles Based on RDE Test with High Load Conditions - Shuai Zhang; Shuxia Miao; Tiebing Song; Zhaoyang Liu; Xu Tian; Jiaxin Gu (Emission Control Science and Technology, 2025)

Investigation of Fuel Injector Orientation Effects on Nitric Oxide (NO) Formation and Emission in a Compression Ignition Engine - M. Ahmed; M. Shakaib; M. Siddiqui (Emission Control Science and Technology, 2025)

The State-of-the-Art in Catalyst Performance Evaluation for Automobile Emission Control in China - Xi Liu; Yuankai Shao; Maoxuan Wang; Anqi Dong; Yatao Liu; Xiaoning Ren; Kaixiang Li; Bingjie Zhou; Weikang Zhu; Hanming Wu; Zhenguo Li (Emission Control Science and Technology, 2025)

Experimental Investigation of the Effect of Al2O3 Nanomaterials as Fuel Additives on Emissions Characteristics of Diesel Engine - Mohamed Kamal Ahmed Ali; Mostafa M. Makrahy (Emission Control Science and Technology, 2025)

Traceable Uncertainty of Exhaust Flow Meters Embedded in Portable Emission Measurement Systems - M. D. Schakel; W. Stiphout; R. Pettinen; Z. Yu; U. Wagner (Emission Control Science and Technology, 2025)
Portable emissions measurement systems (PEMS) are used in the type approval tests of diesel- and petrol-fuelled light-duty vehicles. PEMS measure the amount of pollutants emitted during on-road, real driving, and testing of a vehicle. PEMS are comprised of gas analyzers, which measure the concentration of pollutants in the exhaust gas, and exhaust flow meters (EFMs), which measure the amount of emitted exhaust gas during an on-road test. With the adoption of the real driving emissions (RDE) legislation in 2016–2018, usage of PEMS during on-road tests became mandatory in the European Union for the type approval of light-duty vehicles. For accurate assessment of pollutant emissions, SI-traceable calibration of PEMS equipment is required, which is typically performed under the carefully controlled conditions of a calibration laboratory. However, when using the PEMS equipment in real driving conditions on the road, additional factors contribute to the measurement uncertainty with respect to the laboratory measurement uncertainty as established during the SI-traceable calibration. For this reason, the RDE prescribes the usage of conformity factors to account for additional measurement uncertainty in real-driving-type approval tests. The pollutant emissions measurements are a combination of the gas analyzer measurements and the EFM flow measurement. The EFM measurement uncertainty contributes strongly to the overall pollutant emissions measurement uncertainties. Further, the EFM measurement uncertainty in on-road conditions is not fully characterized. Consequently, SI-traceable, quantitative information on on-road factors affecting measurement uncertainty is needed. Important factors potentially affecting EFM measurement uncertainty are exhaust flow transients, flow pulsations, gas composition, temperature effects, and flow meter drift. For an improved understanding of representative, SI-traceable, EFM measurement uncertainty (I) a generic uncertainty analysis is presented, which is obtained from performing an uncertainty analysis on state-of-the-art knowledge stemming from literature. This is followed by (II) presenting quantitative and partly traceable measurement results of experiments dedicated to the assessment of uncertainty from potentially significant factors contributing to the overall measurement uncertainty of the EFM in on-road conditions. Experimental results indicate that the EFM can match the (laboratory) accuracy limits as defined in the RDE. Other experimental results indicate that specific potential on-road conditions can affect the EFM such that the resulting overall measurement uncertainty exceeds the limit from the employment of the RDE-prescribed conformity factor.

Simplified Analytic Particulate Filter Backpressure Models Revisited: Derivation of the Additive Flow Resistance Model - Timothy C. Watling (Emission Control Science and Technology, 2025)

Nanoparticle Counting for PTI: The Dirty Tail Paradigm — A Pragmatic Proposal to Strongly Reduce Urban PN Pollution from Combustion Engine Fleets - A. Mayer; J. Czerwinski; Th. Lutz; F. Legerer; M. Wyser; P. Comte; L. Larsen; L. Rubino; K. Vasilatou; D. Engelmann; M. Knoll; H. Burtscher (Emission Control Science and Technology, 2025)

Himitsu Bako of NO2 Mixtures: Characterization of NO2 Reference Material Using FTIR Spectroscopy in Middle Infrared Region - Mi Eon Kim; Kirill Berezkin; Jorge Saturno; Viktor Werwein; Gang Li; Alexandra Domanskaya (Emission Control Science and Technology, 2025)
In this work, we investigate how much information a conventional infrared spectroscopic technique (FTIR) can yield for NO 2 reference materials in the range of concentrations between 100 to 2500 μmol/mol. The amount fraction of 100 μmol/mol corresponds to the actual maximum for NO 2 emissions by modern Euro 6 vehicles and is suitable for Portable Emissions Measurement Systems (PEMS) calibration. A set of measurements of four reference mixtures was performed. For the analysis, we developed an efficient and simple algorithm, based on the integration of rovibrational bands, yielding the molar fractions of NO 2 (including dimer) and several impurities, such as N 2 O and HNO 3 . It resembles a Japanese puzzle box, Himitsu Bako, since different mixture components should be addressed in a certain order to unravel a complete composition. The algorithm was successfully applied to the recorded spectra. For example, the uncertainties for low NO 2 amount fractions were shown to be limited essentially by the quality of reference spectroscopic data for the monomer (HITRAN database in the current work), and not by the measurement procedure. Shortcomings, further development, and improvements of the experimental set-up as well as of the evaluation algorithm are addressed.

Influence of Fe3O4 Nanoparticles and Compression Ratio on the Performance Parameters of Diesel Engine Using Tamarind Biodiesel: an Experimental and ANN Analysis - M. Srinivasarao; Ch. Srinivasarao; A. Swarna Kumari (Emission Control Science and Technology, 2025)

Numerical Investigation of the Effects of the Ammonia Injection Rate Shape and Timing on the Performance of an Ammonia-Hydrogen Dual-Fuel Engine - Mahdi Aboujafari (Emission Control Science and Technology, 2025)

Predictive Analysis of Carbon Dioxide Emissions in Heterogeneous Urban Traffic using Neural Networks - Kumkum Bhattacharya; Ketankumar Varmora; Debasis Sarkar; Tolaram Popat (Emission Control Science and Technology, 2025)

Climate and Emissions Benefits of Renewable Diesel: In-Use Testing of a Tier 2 Commercial Harbor Craft - Julia A. Billington; Bo Yang; Wayne Sobieralski; Christian Fehrenbacher; Gavin M. Hoch; Andrew L. Damiano; Razieh Nadafianshahamabadi; Alexander R. Mitchell; David C. Quiros (Emission Control Science and Technology, 2025)

A Comprehensive Study on Hydrocarbon-Based Solutions for Enhanced Diesel Fuel Properties and Engine Emission Reduction - Vipul Saxena; Naveen Kumar; Raghvendra Gautam (Emission Control Science and Technology, 2025)

Engine Exhaust Gas Control of Selective Catalytic System Using Sliding Mode Controller - Devakaran Karaiellapalayam Palanisamy; Arunshankar Jayabalan (Emission Control Science and Technology, 2024)

Examining the Drivers of Environmental Sustainability in OPEC Countries: A Symbiotic Influence Index-STIRPAT-Kaya-EKC Approach - Lamia Ben Amor; Hassen Toumi; Habiba Ameur; Rania Ben Hamida; Hizia Bennia (Emission Control Science and Technology, 2024)

Experimental Investigation of Indirect Aqueous Inoculated Diesel Engine Performance in Urban-Area Driving for Mechanical Performance, Fuel Consumption and NOx Emissions - Asad Asghar Janjua; Waqas Khalid; Samiur Rahman Shah; Emad Ud Din; Usman Bhutta; Majid Ali; Xavier Tauzia (Emission Control Science and Technology, 2024)

The Impact of CO, C3H6, and SO2 on Cu-CHA and V2O5-WO3/TiO2 Catalysts for NH3-SCR for Close-Coupled Operation - Brian B. Hansen; Peter S. Hammershøi; Freja H. Fagerberg; Simon I. Hansen; Xenia B. Sjøgren; Peter N. R. Vennestrøm; Anker D. Jensen; Ton V. W. Janssens (Emission Control Science and Technology, 2024)

Process of SCR Catalyst Deactivation by Dimethylsiloxanes Present in Marine Fuels - Marit Kolb; Lars Wesemann; Peter Eilts; Liliane Fuhrländer; Hubertus Wichmann (Emission Control Science and Technology, 2024)
In recent years, there have been reports of the deactivation of selective catalytic reduction (SCR) exhaust gas catalysts after a short period of operation in marine applications. The trigger and the processes of this catalyst damage have now been investigated experimentally using a fuel burner test bench and various analysis techniques. It was found that organic silicon compounds (OSCs), which are present in marine fuels after use in mineral oil extraction and processing, cause the catalyst deactivation. In practice, these are predominantly dimethylsiloxanes. By the burner experiments, it was found that the OSCs were completely converted into combustion products, in particular SiO 2 . Measurements of particle size distributions and particle number concentrations up- and downstream of the catalyst showed that SiO 2 particles < 20 nm in particular were retained in the catalyst. This filtration effect decreased until no further reduction was observed for particles > 50 nm. Other inorganic, particulate, SiO 2 -containing fuel impurities (catalyst fines) had no poisoning effect here, as these particles are mostly > 50 nm. The small particles formed a closed SiO 2 layer with a thickness of approx. 5 µm on the catalyst surface which grew from the catalyst inlet to the outlet and blocked the catalyst as a diffusion barrier. As the SiO 2 layer increased, the NO conversion rate decreased. The poisoning effects were observed experimentally at OSC concentrations of 5 to 60 mg Si kg −1 fuel. A field-aged catalyst that had been operated on board of a merchant ship revealed the same findings.

Weibull Analysis of DPF Failure Events and Reliability of Diesel Particulate Filters Utilizing After-Sales Maintenance Data - Shirin Ahmadbeigi; Mohammad Ali Ehteram; Abbas Naeimi (Emission Control Science and Technology, 2024)

A Comparison Between the Gaseous and Particulate Emissions from Diesel and Natural Gas Yard Tractors - Tianbo Tang; Hanwei Zhu; Tianyi Ma; Peng Hao; Thomas D. Durbin; Kent C. Johnson; Georgios Karavalakis (Emission Control Science and Technology, 2024)

Effects of Filter Substrate Structure on Flow and Filtration Efficiency of Gasoline Soot - Kazuhiro Yamamoto; Tomoya Aoi (Emission Control Science and Technology, 2024)

A Comparative Study of Platinum- Versus Palladium-Based Catalysts on FeCrAl-Sintered Metal Fiber Filter Substrate for Reducing Gaseous Diesel Engine Emissions - Osama M. Ibrahim (Emission Control Science and Technology, 2024)

Challenges and Solutions to Meet the Euro 7 NOx Emission Requirements for Diesel Light-Duty Commercial Vehicles - Theodoros Kossioris; Robert Maurer; Stefan Sterlepper; Marco Günther; Stefan Pischinger (Emission Control Science and Technology, 2024)
The improvement of air quality requires a further reduction of pollutant emissions, especially in urban areas. The Euro 7 regulations aim at the development of a new generation of internal combustion engine vehicles capable of achieving ultra-low pollutant emissions under demanding, real-world operating conditions. They introduce new technical challenges in the holistic design of a vehicle’s powertrain and emission control system. To identify these, four real-world Euro 7 driving scenarios are investigated, covering demanding urban, highway and mountain driving situations. Technical solutions are then presented to address these challenges and ensure compliance with the Euro 7 emission requirements as set out in the latest regulation proposal of the European Commission. The study focuses on the NOx emissions of an N1 Class III light commercial vehicle with 3.5 t mass and a P2 diesel mild-hybrid powertrain. To ensure emission compliance, a Euro 6e exhaust gas aftertreatment system with enlarged catalysts is combined with NOx raw emission improvements. For low-load cold starts, a 4-kW electric heater in the exhaust system is considered in addition to a 2-l DOC and a 6-l DPF with SCR coating. For high-load cycles with high raw emissions, a 10-l underfloor SCR is considered to ensure the necessary deNOx performance.

A Strategic NH3-Dosing Approach for the Minimization of N2O Production During NH3-SCR Reactions over Cu-SSZ-13 Catalysts - Nicole Daniela Nasello; Nicola Usberti; Isabella Nova; Enrico Tronconi; Frank Hofmann; Simone Dieterich; Marcus Crocoll; Michel Weibel (Emission Control Science and Technology, 2024)
The undesired production of N 2 O during NH 3 -SCR reactions is investigated over a reference commercial Cu-CHA catalyst. Steady-state experiments performed in the 150–500 °C temperature range exhibit a bimodal trend in the N 2 O formation profile, confirming the existence of two different reaction mechanisms occurring at low and high temperatures. Focusing on a low-to-medium T -range, N 2 O production, usually ascribed to NH 4 NO 3 formation and decomposition, increases with the NO 2 /NO x ratio. However, an excess of NO 2 leads to a decrease in the N 2 O release due to ammonium nitrate deposition and catalyst clogging phenomena. Steady-state and dynamics experiments show the promoting effect of both NH 3 feed concentration and NH 3 storage on N 2 O production at T > 200 °C. Surprisingly, N 2 O decreases with increasing NH 3 /NO x ratio at lower temperature. A novel approach based on the strategic injection of NH 3 is also applied to mitigate the N 2 O formation while maintaining high deNO x activity. Remarkably, complete NO x conversion and ~ 11% N 2 O saving are achieved (with inlet NO 2 /NO x = 0–0.5) at temperatures exceeding 200 °C; in addition, a peculiar behavior is observed in the N 2 O profile, which increases and decreases when adding and removing NH 3 from the feed, respectively. Notably, the opposite trend is observed in the N 2 O profile at 200 °C. When under Standard SCR conditions, this so far unreported observation challenges the NH 4 NO 3 formation route for N 2 O and suggests the existence of different controlling phenomena at different temperature regimes: i) the Cu/redox chemistry at T ≤ 200 °C and ii) the NH 3 storage at higher temperature, ideally up to 300 °C.

An Adaptive Estimation Approach for Integrating Real-World Operation Dynamics in Engine-Out NOx Emission Modeling of a Wheel Loader - Beichuan Hong; Wilco Burghout (Emission Control Science and Technology, 2024)
Accurately predicting engine-out nitrogen oxides (NOx) emissions on-board is crucial for effective emission control in heavy-duty engines. Real-world engine operating conditions, especially in non-road applications with frequent dynamic changes, can significantly affect NOx emission characteristics. However, these engine emission characteristics are conventionally measured on steady-state or regulated driving cycles, which may not fully reflect the emission levels under real-world operational dynamics. This highlights the necessity of integrating engine performance during transient operation into the NOx prediction model to enhance the accuracy of on-board predictions. This paper introduces a novel data-driven model to predict engine-out NOx emissions during the construction activities of a wheel loader. This paper begins by addressing discrepancies between steady-state map predictions and on-board NOx measurements. To bridge these gaps, the model identifies engine transient operating conditions by analyzing the time derivatives of engine speed and torque. The model structure integrates steady-state and transient emission maps, with the transient map being iteratively refined using the Kalman filter principle, thereby improving its accuracy and robustness in response to engine dynamics. The proposed method maintains a model structure that is easily implemented and similar to conventional steady-state emission maps, while also enabling online self-learning for model parameter updates. Model validation shows that the model has high prediction accuracy and the ability to differentiate between steady-state and transient engine working conditions during construction activities.

Research on Regeneration Technology for Gasoline Particulate Filters Using Microwave Heating - Toru Uenishi; Kazuhiko Koike; Takumi Suzawa (Emission Control Science and Technology, 2024)

Reduction of Emissions in Diesel Engine Using Blended Diesel with Edible Bran Oil - A. K. Singh; S. Barman; P. Mondal; N. Barman (Emission Control Science and Technology, 2024)

Particulate Filters for Combustion Engines to Mitigate Global Warming. Estimating the Effects of a Highly Efficient but Underutilized Tool - Andreas C.R. Mayer; Joerg Mayer; Max Wyser; Fritz Legerer; Jan Czerwinski; Thomas W. Lutz; Timothy V. Johnson; Mark Z. Jacobson (Emission Control Science and Technology, 2024)
Particulate filters are state-of-the-art and are used in internal combustion engines worldwide to eliminate carcinogenic nanoparticles. Health studies estimate that this prevents about one million premature deaths annually. What is less known and often neglected is their equally powerful effect on mitigating global warming. This is because these ultrafine particles form stable aerosols in the atmosphere, absorb sunlight, and heat the atmosphere due to their jet-black color. In addition, once deposited on the ground, they reduce albedo especially when deposited on ice or snow. They also thin clouds and reduce their reflectivity. In this paper, we estimate for the first time the cumulative effect of more than 300 million particulate filters currently installed globally on vehicles, showing that, while they reduce ~ 0.5 Mt of soot per year, their effect on slowing global warming is equivalent to reducing 1 Bt of CO 2 per year or about one-third of the CO 2 emissions of all European Union Member States combined. Despite its strong potential, this highly efficient, proven, and low-cost technology is not yet regarded as a priority in curbing global warming, even though it is possibly the easiest and quickest to implement. If used in retrofitting more diesel and petrol engines worldwide, it could triple the aforementioned effect. While modern internal combustion engines are on track to be replaced with zero-emission vehicles, it is also crucial, and we strongly suggest that, in the interim, all remaining internal fossil fuel combusting engines be fitted with particulate filters. Evidence is presented in this paper that the potential benefits of such retrofit on climate and human health will be impactful and lasting.

Forced Convection Heat Transfer Characteristics of Developed Laminar Flow in the Octagonal Channels of Octo-Square Asymmetric Particulate Filters - Timothy C. Watling (Emission Control Science and Technology, 2024)

Emissions from the Construction Sector in the United Kingdom - Carl Desouza; Daniel Marsh; Sean Beevers; Nick Molden; David Green (Emission Control Science and Technology, 2024)
The UK national atmospheric emissions inventory estimates of construction industry emissions use a top-down approach, based on fuel consumption and employment. It estimates that the sector is the 2nd largest emitter of PM 2.5 (14%) and 4th largest emitter of NO X (7%). In this study, we have adopted a bottom-up approach to assess emissions of NO X from the sector and show that emissions are 39% higher than the existing estimates. By developing a novel fleet turnover model to predict the population and emission standard of construction machinery up to 2025, we demonstrate a significant shift in the quantity and types of machines used. The overall uncertainty of the model was calculated to be 55%. Applying the estimated uncertainties to the model, in 2018, the non-road mobile machinery fleet in the UK emitted 36.6 ± 10.0 kilo-tonnes of NO X , whilst the NAEI estimated 33.2 kilo-tonnes for the same sector. For the subsequent years 2019 and 2020, the NAEI estimate was within the model’s uncertainty prediction—28.0 kilo-tonnes compared with 32.7 ± 8.9 kilo-tonnes for 2019 and 23.2 kilo-tonnes compared with 29.5 ± 8.1 kilo-tonnes for 2020. Overall, the size of the non-road mobile machinery fleet in the UK is predicted to reduce by 4% in 2025 compared to 2018. Furthermore, the introduction of Stages IV and V emission regulations for new machines will lead to a 58% reduction in fleet NO X emissions over the same period. These emission regulations are targeted at the larger, more polluting machines, with smaller machines not required to meet tighter emissions standards under Stage V. As a result, mini-excavators are the most common machines and consequently become the dominant source of NO X emissions from the fleet, contributing 55% in 2025. Therefore, tighter emissions regulations, or the uptake of battery power in the form of electrification, for these small machines would yield significant emissions reductions. Graphical Abstract

Combined Ash and Soot Monitoring for Gasoline Particulate Filters Using a Radio-Frequency-Based Sensor - Stefanie Walter; Peter Schwanzer; Gunter Hagen; Hans-Peter Rabl; Markus Dietrich; Ralf Moos (Emission Control Science and Technology, 2024)
Increasingly stringent emission limits have made particulate filters necessary for gasoline engines. Similar to diesel applications, gasoline particulate filters (GPFs) can be monitored by differential pressure measurement or by the radio-frequency-based filter diagnosis (RF sensor). In addition to measuring the soot loading, ash detection is critical for monitoring the GPF over the entire vehicle lifetime. Because the RF sensor detects the filter loading through a change in the dielectric properties of the GPF, it can detect not only soot but also ash. In diesel applications, the RF sensor has already demonstrated its potential for ash detection. To verify the feasibility of simultaneous ash and soot monitoring for GPFs, filters were loaded with ash on an engine test bench and measured on a lab test bench under defined synthetic exhaust gas conditions. By evaluating resonant modes, soot and ash could be clearly distinguished, as ash mainly affects the resonant frequency, while soot also changes the quality factor due to its high dielectric losses. However, higher soot loadings could not be detected by the resonant parameters, but instead by a frequency-averaged transmission signal. While the presence of ash caused an offset in this signal, its sensitivity to soot was not affected. Thus, the influence of ash can be corrected if the signal in the soot-free filter state is known, e.g., from the behavior of the resonant parameters. Therefore, even with a continuously increasing ash loading over the lifetime of a vehicle, an accurate soot detection is possible with the RF sensor.

A Thermodynamics Model for the Assessment and Optimisation of Onboard Natural Gas Reforming and Carbon Capture - Li Chin Law; Epaminondas Mastorakos; Mohd. Roslee Othman; Antonis Trakakis (Emission Control Science and Technology, 2024)
The paper examines pre-combustion carbon capture technology (PreCCS) for liquefied natural gas (LNG) propelled shipping from thermodynamics and energy efficiency perspectives. Various types of LNG reformers and CCS units are considered. The steam methane reformer (SMR) was found to be 20% more energy efficient than autothermal (ATR) and methane pyrolysis (MPR) reactors. Pressure swing adsorption (PSA) had a lower energy requirement than membrane separation (MEM), cryogenic separation (CS), and amine absorption (AA) in pre-combustion carbon capture, with PSA needing 0.18 kWh/kg CO 2 . An integrated system combining SMR and PSA was proposed using waste heat recovery (WHR) from the engine, assuming similar efficiency for LNG and H 2 operation, and cooling and liquefying of the CO 2 by the LNG. The SMR-PSA system without WHR had an overall efficiency of 33.4% (defined as work at the propeller divided by the total LNG energy consumption). This was improved to 41.7% with WHR and gave a 65% CO 2 emission reduction. For a higher CO 2 reduction, CCS from the SMR heater could additionally be employed, giving a maximum CO 2 removal rate of 86.2% with 39% overall energy efficiency. By comparison, an amine-based post-engine CCS system without reforming could reach similar CO 2 removal rates but with 36.6% overall efficiency. The advantages and disadvantages and technology readiness level of PreCCS for onboard operation are discussed. This study offers evidence that pre-combustion CCS can be a serious contender for maritime propulsion decarbonization. Graphical Abstract

Assessment of On-Road High NOx Emitters by Using Machine Learning Algorithms for Heavy-Duty Vehicles - Filiz Kazan; Arvind Thiruvengadam; Marc C. Besch (Emission Control Science and Technology, 2023)

Impact of COVID-19 Pandemic on Greenhouse Gas Emissions in Iran: an Environmental Input-Output Approach - Ali Faridzad (Emission Control Science and Technology, 2023)

The Effect of Catalyst Composition on Electric Field-Mediated Catalytic Reactions for Exhaust Emission Control - Toru Uenishi; Yasushi Sekine (Emission Control Science and Technology, 2023)

Influence of Asymmetric Channel Structure on Capture and Regeneration Process of Diesel Particulate Filter - Dong Tang; Pengfei Zhang; Yubin Han; Yang Liu (Emission Control Science and Technology, 2023)

In Situ Tracking of Break-up, Resuspension, and Transport of Reactive Particle Structures in a Single Wall-Flow Filter Channel - Julia R. D. Thieringer; Heike Werling; Jörg Meyer; Achim Dittler (Emission Control Science and Technology, 2023)
Particulate filters are used as a standard component in the exhaust gas aftertreatment of vehicles. The reactive (soot) and inert (ash) particles generated during engine operation are deposited in wall-flow filter. The resulting particle layer increases the differential pressure of the filter, which is why it is regenerated regularly. During regeneration of the filter, the reactive particles oxidize, and the inert particles remain in the filter. The oxidation of the soot particles results in a layer break-up, and the resuspension of particle structures can occur. The layer break-up over the entire length of an inlet channel and the resuspension of particle structures have not yet been observed, which is why the fundamental processes in a particulate filter have not yet been fully clarified. In these investigations, the regeneration of a single wall-flow filter channel is observed in situ with high temporal and spatial resolution. For this purpose, the filter is loaded with soot particles and regenerated subsequently. The regeneration of the filter is analyzed in relation to the process parameters of temperature, layer thickness, and flow velocity. Before the visual layer break-up, the pressure drop decreases and declines to a constant value before resuspension of particle structures are detected. As the temperature is increased, the regeneration time is reduced. With a thicker particle layer, the particle structures formed during layer break-up become larger, the location of resuspension shifts to the posterior channel region, and the number of resuspensions increases. A higher flow velocity causes more particle structures to be resuspended and transported to the channel end.

Simulating Catalytic Reaction and Soot Oxidation in Coated Particulate Filters: a Simplified Modelling Framework Including Diffusion Effects - Timothy C. Watling (Emission Control Science and Technology, 2023)

An Experimental Study on the Conversion of CaO to CaSO4 During Diesel Particulate Filter Regeneration - Kotaro Tanaka; Yasuyuki Sakai; Yudai Ishii; Yusuke Yokobayashi; Satoshi Sakaida; Mitsuru Konno (Emission Control Science and Technology, 2023)

Coupling of Liquid and Surface Chemistry in Urea SCR Systems - Christian Kuntz; Paul Jakob Jägerfeld; Joe Mmbaga; Robert E. Hayes; Olaf Deutschmann (Emission Control Science and Technology, 2023)
Close-coupled selective catalytic reduction (SCR) systems are one method to deal with tightening emission legislation for NO x in internal combustion engines. Due to smaller mixing sections and at unfavourable boundary conditions, however, urea-water solution (UWS) droplets can impact on the SCR catalyst itself. To investigate this phenomenon further, this work develops a modeling capability of this process. Established mechanism for NH 3 -SCR and HNCO hydrolysis from literature is integrated into DETCHEM CHANNEL and a 2D COMSOL model to simulate the influence in the SCR Channel. Simulations are validated against end-of-pipe experiments from literature and spatially resolved concentration profiles from a hot gas test rig with very good agreement. Finally, a channel simulation is coupled with a model to describe the catalytic decomposition of an urea droplet. The coupled simulation is able to simulate the influence of UWS droplet impact onto a catalyst channel. Fast droplet decomposition causes a peak in NH 3 and HNCO in the single channel and thus increases NO x conversion. However, the overall uniformity and efficiency are decreased, which is why droplet impact on the catalyst should be strictly avoided.

Particle Number Emission for Periodic Technical Inspection in a Bus Rapid Transit System - Maria L. Botero; Javier Londoño; Andrés F. Agudelo; John R. Agudelo (Emission Control Science and Technology, 2023)
This study was carried out under the Climate and Clean Air in Latin American Cities program (CALAC+) and aimed to evaluate the particle-number-based periodic technical inspection (PN-PTI) test in a public bus rapid transport (BRT) system and establish a baseline of PN emission. The PN-PTI test was performed in 1474 buses with emission standards from Euro II to Euro V without diesel particle filter (DPF), Euro V with retrofitted DPF, Euro VI diesel with original engine manufacturer DPF, and compressed natural gas (CNG) fueled. The median PN emission of buses with DPF is below 3000 #/cm 3 . PN emission limits such as 1,000,000 #/cm 3 or 250,000 #/cm 3 would allow the approval of vehicles with DPF that are not fully operational. An additional high-idle test is proposed for buses with emissions above 50,000 #/cm 3 , but below the test approval limit, to detect DPF that may require maintenance.For buses without DPF, which are the majority of the bus fleets in Latin America, the PN emission test can detect and target very-high emitters for developing special policies. CNG buses presented the lowest emissions, likely because of the detection limit of the equipment (23 nm) which cannot detect the large number of particles emitted by these vehicles in the sub-23 nm particle range.

Deterioration in Emissions from Light Vehicles in Use Converted to CNG (Bi-Fuel) - Julio Vassallo; Eduardo Miró (Emission Control Science and Technology, 2023)

Effect of Metallic Microfiber Flow Through Diesel Particulate Filter System on Diesel Engine’s Particle Emission Physicochemical Characteristics - Ban-seok Oh; Poonnut Thaeviriyakul; Watanyoo Phairote; Mek Srilomsak; Chinda Charoenphonphanich; Watcharin Po-ngaen; Sompong Srimanosaowapak; Katsunori Hanamura; Preechar Karin (Emission Control Science and Technology, 2023)

Real-World Evaluation of Pollutant Emissions from a Light-Duty DI-Gasoline Hybrid Electric Vehicles (HEV) Using PEMS - Chengguo Li; Susumu Sato; Tianyi Ma; Kent C. Johnson; Thomas Durbin; Georgios Karavalakis (Emission Control Science and Technology, 2023)

Ion Mobility Spectrometry Towards Environmental Volatile Organic Compounds Identification and Quantification: a Comparative Overview over Infrared Spectroscopy - Pedro Catalão Moura; Valentina Vassilenko; Paulo António Ribeiro (Emission Control Science and Technology, 2023)
Volatile organic compounds (VOCs) can be extremely toxic and hazardous to expose humans in both indoor and outdoor environments; thus, their detection, correct identification, and accurate quantification are relevant and demanding tasks that need to be addressed. Fortunately, several known analytical techniques allow the qualitative and quantitative assessment of these compounds. This review paper stresses on two independent spectroscopic techniques, infrared spectroscopy and ion mobility spectrometry, both suitable for the detection of very small concentration levels of VOCs in gaseous samples. Infrared spectroscopy is a well-known technique that has been largely applied per se or combined with additional methodologies, to study VOCs at both high and low concentration levels. On the other hand, ion mobility spectrometry gained relevance in this field, due to its capability to measure trace concentration levels, namely ppb v and even ppt v . For this review paper, several scientific papers were analyzed, and the most relevant were addressed throughout the text. The working principles of both techniques are carefully addressed, and updated data is provided for highlighting the advantages and disadvantages of both techniques for the environmental VOCs assessment in air quality control.

Experimental Investigation on Impact of Diethyl Ether Additives with Cashew Nut Shell Liquid Biodiesel Blends on Performance Characteristics of Engine Operating at Optimum Conditions - D. Senthil kumar; Sivanesan Murugesan (Emission Control Science and Technology, 2023)

Evaluation of On-Board Sensor-Based NOx Emissions from the Heavy-Duty Vehicles in an Inspection and Maintenance Program - Chengguo Li; Tianyi Ma; Georgios Karavalakis; Kent C. Johnson; Thomas D. Durbin (Emission Control Science and Technology, 2023)

Transient Flow Uniformity Evolution in Realistic Exhaust Gas Aftertreatment Systems Using 3D-CFD - Pratheeba Chanda Nagarajan; Henrik Ström; Jonas Sjöblom (Emission Control Science and Technology, 2022)
To precisely control a vehicle powertrain to minimize emissions, accurate and detailed models are needed to capture the spatio-temporal variability of the variables of interest. The aim of this work is to analyze flow and temperature fields in a geometrically realistic — and thus complex — exhaust gas aftertreatment system under transient conditions. The spatio-temporal response of these fields to upstream step changes is predicted using three-dimensional unsteady Reynolds-averaged Navier-Stokes (URANS) $$κ - ω$$ κ - ω simulations where the catalytic converter is described as a porous medium. A catalytic converter geometry with a 90 $$^{° }$$ ∘ -bend and a partially dead volume is used to demonstrate the effects of time-resolved flow maldistribution on the profiles of velocity and temperature. Two sets of transient simulations in terms of step changes in velocity and temperature are performed. Uniformity indices are used to characterize the distribution and variability of the different catalyst channels under transient conditions. The evolution of the uniformity indices as functions of time and axial distance into the catalyst are calculated at different cross-sectional planes. The results show that the evolution of the temperature uniformity is rate controlling, continuously modulating the otherwise much faster flow uniformity response via the fluid properties. The temperature uniformity time scale is determined by the balance of flow, thermal inertia, and the heat losses from the system. The interplay between pressure drop and heat losses governs the transition to the new steady state in uniformity. These types of transient simulations and analyses can contribute essential information when developing reduced-order engineering models to represent the spatio-temporal variability in exhaust aftertreatment systems, in particular during rapid events such as cold start.

Studies on the Effect of Swirl on Nitric-Oxide Formation in Combustion—a Selected Review - L. X. Zhou; F. Wang; Y. Zhang (Emission Control Science and Technology, 2022)

Steady-State NOx Emission Model for Gas-Fired Heating and Hot Water Combi-Boilers with Factor Analysis and Artificial Neural Network - Weiye Zhou; Wenxue Gao; Hongting Ma; Wenbo Liu; Lijie Yang; Lin Yang (Emission Control Science and Technology, 2022)

Effects of Wall-Ash and Plug-Ash on Pressure Drop and Soot Deposition in Diesel Particulate Filter - Kazuhiro Yamamoto; Takuya Morimoto (Emission Control Science and Technology, 2022)

Simplified Analytic Particulate Filter Backpressure Models, including the Additive Flow Resistance Model - Timothy C. Watling (Emission Control Science and Technology, 2022)

In-use Emission Measurements from Two High-Speed Passenger Ferries Operating in California with Tier 2 and Tier 3 Marine Diesel Engines - Chas Frederickson; Heejung S. Jung; Wei Liu; Trevor S. Krasowsky; Mark Villela; Haiko Rading; Stefan Mussotter; David C. Quiros (Emission Control Science and Technology, 2022)

Influence of Global Operating Parameters on the Reactivity of Soot Particles from Direct Injection Gasoline Engines - S. Koch; F. P. Hagen; L. Büttner; J. Hartmann; A. Velji; H. Kubach; T. Koch; H. Bockhorn; D. Trimis; R. Suntz (Emission Control Science and Technology, 2022)
The aim of this study is to investigate the impact of global operating parameters, e.g., engine speed, brake mean effective pressure, and air–fuel ratio, of a turbocharged 4-cylinder GDI engine on the reactivity of soot particles against oxidation. The knowledge of soot reactivity is crucial for optimizing gasoline particulate filter regeneration strategies and is, consequently, a key parameter for reducing fuel consumption and CO 2 emissions. In this work, time-resolved in-cylinder soot concentrations and exhaust particle size distributions are measured by using two-color pyrometry, engine exhaust particle sizer and smoke meter, respectively. Reactivity against oxidation by molecular oxygen is determined by temperature programmed oxidation analysis. To derive a physicochemical explanation for varying soot reactivity, the morphological and nanostructural primary particle structure of collected samples is analyzed using high-resolution electron microscopy and image analysis algorithms. The results reveal that engine operating parameters affect soot reactivity differently. While engine speed has only a slight effect, a reduction of air/fuel ratio ( λ < 1.0) or an increase of BMEP > 10 bar significantly reduces the soot oxidation reactivity. These findings give evidence, that the quality of the fuel/air mixture is a significant parameter influencing soot reactivity. Measured soot concentrations substantiate the hypothesis that low-sooty homogeneous premixed combustion of a homogeneous fuel/air mixture favors formation of high-reactive soot particle fractions. Reactive soot particle aggregates are composed of multiple soot fractions of different reactivity. Reactive primary particles are composed of short graphene-like layers and vice versa, providing a physicochemical explanation for varying soot reactivity depending on engine operating conditions.

Effect of Rare-Earth (La, Nd, Pr, Y) Doping on the Properties of X-Y-Ce-Zr-O and X-Y-Z-Ce-Zr-O Nanodispersions for GPF Applications - I. Wiseman; L. Roebuck; D. Scapens (Emission Control Science and Technology, 2022)

Implications of Hydrated Ash on Filtration Efficiency and Performance of Particulate Filters (DPF, GPF, and SCRF)—a Perspective - Sujay Bagi; Carl Justin Kamp (Emission Control Science and Technology, 2022)

Experimental and Modeling Study of NO and NO2 Storage and Release Characteristics of a Diesel-Cold Start Catalyst - Boopathi S. Mahadevan; Conor T. Berndt; John H. Johnson; Jeffrey D. Naber (Emission Control Science and Technology, 2022)

Experimental and Numerical Analysis of an Innovative Mixer Geometry for Urea Injection in SCR Applications - Federico Millo; Francesco Sapio; Benedetta Peiretti Paradisi; Andrea Bianco; Lucio Postrioti; Giacomo Buitoni; Marco Tabarrini; Cristina Robino (Emission Control Science and Technology, 2022)
Selective catalytic reduction (SCR), based on the injection of urea-water-solution (UWS), is one of the prevailing and more effective approaches to reduce NOx emissions in diesel engines. To improve the performance and durability of the system, it is crucial to develop reliable simulation tools able to correctly describe not only the urea conversion into ammonia and the mixing with exhaust gases but also the possible formation of solid deposits along with the engine’s exhaust line. In the present paper, two different exhaust systems for off-road applications are analyzed, both of them consisting of a diesel oxidation catalyst (DOC) followed by a diesel particulate filter (DPF), a UWS injection and a mixing device, and an SCR catalyst. Two alternative UWS mixing subsystems are evaluated, including a newly developed design. A 3D-CFD numerical analysis is carried out to assess the performance of both systems in terms of pressure drop, UWS spray, and liquid film development, in addition to flow velocities and species concentration uniformities at SCR catalyst inlet. A detailed analysis of droplet impingement on walls and liquid film development is enabled, thanks to a conjugate heat transfer (CHT) approach. Moreover, a deposit risk index is used to identify the areas of the systems where urea deposit formation is expected. Eventually, numerical results are compared with experiments on one operating condition chosen as the most challenging in terms of exhaust temperature and flow rate, both in terms of systems NO x conversion efficiency and deposit formation, showing a satisfactory agreement, thus paving the way to use the proposed synergetic numerical and experimental approach to further optimize the design and the system’s performance.

The Effect of Variable Overlap and Primary Particle Size on Fractal-Like Aggregate Mobility Diameter and Effective Density - Maria Syrigou; Ioanna Marina Anagnostara; Athanasios G. Konstandopoulos (Emission Control Science and Technology, 2022)

Investigation of CO Deactivation of Passive NOx Adsorption on La Promoted Pd/BEA - Rojin Feizie Ilmasani; Phuoc Hoang Ho; Aiyong Wang; Dawei Yao; Derek Creaser; Louise Olsson (Emission Control Science and Technology, 2022)
Passive NO x adsorption (PNA) is a method, in which NO x can be stored at low temperatures and released at higher temperatures where the urea decomposition is functional during selective catalytic reduction (i.e., above 180–200 °C). We have studied the promotion of Pd/BEA with La as a PNA in the presence of high CO concentration. Both the reference and promoted samples exhibited a significant loss of NO x adsorption/desorption capacity after multiple cycles using 4000 ppm CO. However, already after 5 cycles, 99% of the NO x released between 200 and 400 °C was lost for Pd/BEA, compared to only 64% for Pd-La/BEA, which thereafter was stable. XPS and O 2 -TPD clearly showed that the Pd species were influenced by La. The PNA deactivation in the presence of CO could be related to Pd reduction followed by migration and the formation of more PdO x clusters, as observed by O 2 -TPD analysis. Interestingly, significantly more PdO x clusters formed on Pd/BEA after 10 cycles compared to Pd-La/BEA.

AdSCR Systems (Adsorption + Selective Catalytic Reduction): Analysis of the Influence of H2O and CO2 on Low Temperature NOx Emission Reduction Performances - Nicole Daniela Nasello; Federica Gramigni; Isabella Nova; Enrico Tronconi (Emission Control Science and Technology, 2021)

Numerical Prediction of Particulate Matter (PM) Collection Efficiency, Loading, and Flow Characteristics in Partially Damaged Particulate Filters with Different PM Size Classes - T. Chittipotula (Emission Control Science and Technology, 2021)

Backpressure Prediction for Flow-Through Monoliths and Wall-Flow Filters Using 1-Dimensional Models: Entrance Effect Pressure Change, Developing Flow and Validation Using Length-Varying Techniques - Timothy C. Watling; Yolanda Van Lishout; Ian D. Rees (Emission Control Science and Technology, 2021)

Comparative Study of SO2 and SO2/SO3 Poisoning and Regeneration of Cu/BEA and Cu/SSZ-13 for NH3 SCR - Xavier Auvray; Maria Arvanitidou; Åsa Högström; Jonas Jansson; Sheedeh Fouladvand; Louise Olsson (Emission Control Science and Technology, 2021)
Two copper-exchanged zeolites, Cu/SSZ-13 and Cu/BEA, were studied as catalysts for the selective reduction of NO x by NH 3 (NH 3 -SCR). Their activities for standard SCR (NO x = NO) and fast SCR (NO x = 50% NO + 50% NO 2 ) were measured before and after sulfur poisoning at 250 °C. The effect of 30 ppm SO 2 and a mixture of 24 ppm SO 3 + 6 ppm SO 2 was evaluated. The repetition of subsequent activity measurements served as regeneration method in SCR conditions. SO 2 deactivated Cu/SSZ-13 whereas Cu/BEA was only moderately affected. SO 3 led to stronger deactivation of both catalysts than SO 2 . However, also for this case, the Cu/BEA was significantly less affected than Cu/SSZ-13, even though Cu/BEA contained larger amount of stored sulfur. One possible reason for this could be the large pores of Cu/BEA, where the sulfur species possibly resulted in less sterical hindrance than in the small pore SSZ-13 structure. NH 3 temperature-programmed desorption (NH 3 -TPD) showed no loss of storage sites upon sulfur treatment and subsequent regeneration. Partial activity recovery was observed after a period in SCR conditions at 400 °C and 500 °C. Temperature at 300 °C was insufficient to regenerate the catalysts. Diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS) of NO adsorption suggested that SO 2 interacts with the ZCuOH sites on Cu/SSZ-13, causing the strong poisoning.

Light-off Investigation of Oxymethylene Ether (OME) Considering the Presence of the Exhaust Components Heptane, Carbon, and Nitrogen Monoxide - Florian Rümmele; Alexander Susdorf; Syed Muhammad Salman Haider; Robert Szolak (Emission Control Science and Technology, 2021)
Synthetic fuels and fuel blends like OMEs can contribute to tank-to-wheel CO 2 emission savings. At the same time, it is known that these fuels have a lower exhaust temperature compared to conventional diesel. This effect has major impact on the exhaust after-treatment system, particularly in cold start conditions. This paper investigates the light-off behavior of exhaust gases containing OMEs by temperature-programmed oxidation experiments using a state-of-the-art oxidation catalyst. The main side product of catalytic oxidation of OMEs between 100 °C and the oxidation temperature T 50 , which was around 160 °C, was shown to be formaldehyde. While alkane oxidation, in this case heptane, was little influenced by OME oxidation, the oxidation temperature T 50 of CO increases by more than 10 °C by OME addition. Nitrogen monoxide impeded the oxidation of OME in a similar way to the other components investigated. Due to the amount of FA produced and its toxicity, it could be concluded that it is necessary to heat up exhaust after-treatment systems of OME diesel engines even faster than conventional diesel exhaust after-treatment systems. The relatively high reactivity of OME on oxidation catalyst can be used by active thermal management approaches.

Influence of V2O5 and AlF3 on Microstructure of Acicular Mullite Diesel Particulate Filter Along with Soot Oxidation Kinetics - Eakkawut Saenkhumvong; Preechar Karin; Swe Zin Win; Settavit Sirivarocha; Nuwong Chollacoop; Katsunori Hanamura (Emission Control Science and Technology, 2021)

Cold-Start Modeling and On-Line Optimal Control of the Three-Way Catalyst - Jonathan Lock; Kristoffer Clasén; Jonas Sjöblom; Tomas McKelvey (Emission Control Science and Technology, 2021)
We present a three-way catalyst (TWC) cold-start model, calibrate the model based on experimental data from multiple operating points, and use the model to generate a Pareto-optimalcold-start controller suitable for implementation in standard engine control unit hardware. The TWC model is an extension of a previously presented physics-based model that predicts carbon monoxide, hydrocarbon, and nitrogen oxides tailpipe emissions. The model axially and radially resolves the temperatures in the monolith using very few state variables, thus allowing for use with control-policy based optimal control methods. In this paper, we extend the model to allow for variable axial discretization lengths, include the heat of reaction from hydrogen gas generated from the combustion engine, and reformulate the model parameters to be expressed in conventional units. We experimentally measured the temperature and emission evolution for cold-starts with ten different engine load points, which was subsequently used to tune the model parameters (e.g. chemical reaction rates, specific heats, and thermal resistances). The simulated cumulative tailpipe emission modeling error was found to be typically − 20% to + 80% of the measured emissions. We have constructed and simulated the performance of a Pareto-optimal controller using this model that balances fuel efficiency and the cumulative emissions of each individual species. A benchmark of the optimal controller with a conventional cold-start strategy shows the potential for reducing the cold-start emissions.

Emission Reduction Efficiency Analysis Based on Characteristics of Vehicle Emissions - Yi Xu; Yujiao Hao; Tongqing Zhang; Wei Yan; Yuqiong Wang; Dong Guo; Xiaochuan Tan; Xingbang Gao; Jiaojiao Li (Emission Control Science and Technology, 2021)

Modelling Investigation of the Thermal Treatment of Ash-Contaminated Particulate Filters - Chung Ting Lao; Jethro Akroyd; Alastair Smith; Neal Morgan; Kok Foong Lee; Daniel Nurkowski; Markus Kraft (Emission Control Science and Technology, 2021)
This paper investigates the impact of thermal treatment on the pressure drop of particulate filters containing ash deposits. A one-dimensional model has been developed and applied to describe the deposition of soot and ash particles, and estimate the spatial distribution of the deposits in such filters. Phenomenological models have been developed to describe the potential sintering and cracking of the ash deposits caused by thermal treatment of the filter. The model results are in good agreement with experimental measurements of the reduction in the pressure drop in thermally treated filters. It was found that crack formation in the ash layer can lead to significant reduction of the pressure drop at relatively low temperatures. Sintering of ash deposits in the wall and the ash plug also contributes towards a decrease in filter pressure drop at higher temperatures. This work is the first attempt to model the impact of the thermal treatment of ash in particulate filters in order to support the development of future ash management strategies. The cracking of the ash layer during the thermal treatment has been identified to be the most critical effect for pressure drop reduction.

Influence of Preparation Conditions on Platinum and Palladium Catalysts Supported on Anodically Oxidized Stainless Steel Wire Meshes for CO Oxidation - Michael M. Royko; Savannah Howell; Ehsan Faegh; William Mustain; Jochen Lauterbach (Emission Control Science and Technology, 2021)

Impact of Different Synthesis Methods on the Low-Temperature Deactivation of Cu/SAPO-34 for NH3-SCR Reaction - Jungwon Woo; Aiyong Wang; Diana Bernin; Homayoun Ahari; Mark Shost; Michael Zammit; Louise Olsson (Emission Control Science and Technology, 2021)

Improved Pressure Drop Modeling During Regeneration of Particulate Filters Using Soot Cake with Variable Porosity - Wen Wang; Robert R. O. Brydon; Edward J. Bissett; Syed Wahiduzzaman (Emission Control Science and Technology, 2021)

Evaluation of a Catalyzed Diesel Particulate Filter Coated by a Novel Silver-Based Catalyst Using Mining Diesel Engines - Lioudmila Nossova; Gianni Caravaggio; Brent Rubeli; David Young (Emission Control Science and Technology, 2021)

Statistical Approach to Diesel Aftertreatment Accelerated Aging Performance Correlation to In-Use Population - Homayoun Ahari; John Phillips; Thomas Pauly (Emission Control Science and Technology, 2021)

Particle Size-Dependent Filtration Efficiency and Pressure Drop of Gasoline Particle Filters with Varying Washcoat Volumes - Xiangxiao Kong; Kerry Chen; Robert Greiner; Martin Votsmeier; Igor Belot; David Vidal; François Bertrand; Robert E. Hayes; Jason S. Olfert (Emission Control Science and Technology, 2021)

Estimating Road Transport Pollutant Emissions Under Traffic-Congested Conditions with an Integrated Modelling Tool—Emissions Reduction Scenarios Analysis - Natalia Liora; Anastasia Poupkou; Serafim Kontos; Charikleia Meleti; Katerina Chrysostomou; Georgia Aifadopoulou; Stella Zountsa; Chrisostomos Kalogirou; Ricardo Chacartegui; Francesca Liguori; Massimo Bressan; Susana Marta Almeida; et al. (Emission Control Science and Technology, 2021)

Physicochemical Characterization of Diesel Engine’s Soot and Metal Oxide Ash Nanoparticles Using Electron Microscopy, EDS and TGA - Preechar Karin; Phyozin Koko; Chinda Charoenphonphanich; Nuwong Chollacoop; Katsunori Hanamura (Emission Control Science and Technology, 2021)

Modelling of Mass Transfer Resistances in Non-uniformly Washcoated Monolith Reactors - M. Walander; J. Sjöblom; D. Creaser; B. Agri; N. Löfgren; S. Tamm; J. Edvardsson (Emission Control Science and Technology, 2021)
There are various methodologies to account for mass transfer within non-uniformly distributed washcoats in monolith reactors in 1D models (axially). However, 1+1D models (axially/radially) fail to capture local variations in mass transfer from different coating thicknesses or cracks. In this paper, we present a novel way to account for local material properties in a washcoated monolith reactor. The suggested method uses an existing 1+1D modelling framework and sectionalizes the washcoat into multiple tangential segments which are solved independently. Intelligent gravimetric analysis and scanning electron microscopy are used in combination to calculate local effective diffusivity as an input for each simulation. The new model is compared to the original 1+1D model using NO light-off simulations. The new model predicted increased conversion at elevated temperatures, where mass transfer limitations are present, due to the higher porosity in the corners. The simulation time for each model was similar due to the parallelizable nature of the new model.

Calibration Uncertainty of 23nm Engine Exhaust Condensation Particle Counters with Soot Generators: a European Automotive Laboratory Comparison - Alexander Terres; Barouch Giechaskiel; Andreas Nowak; Volker Ebert (Emission Control Science and Technology, 2021)
Calibration of condensation particle counters (CPC) to measure non-volatile particle number (PN) from vehicle emissions is a significant source of uncertainty of the regulated particle number measurements. In this work, the calibration uncertainty of automotive and calibration laboratories was determined in a first-of-its-kind comparison. For this purpose, the counting efficiency of a reference CPC for automotive exhaust emission measurements was determined at seven participants across Europe with ten soot aerosol generators. Calibration uncertainty was found to be very different in the CPC’s cut-off regime (around the D 50 of 23nm) with a coefficient of variation (CoV) of 11% and the plateau regime (from the D 90 of 41nm upwards) with a CoV of 4.5%. The uncertainty was higher for a group of soot generators with poorly optimized operating points with a CoV of 31% at 23nm and 5.8% at ≥41nm. Specific influence factors on the calibration uncertainty (measured as the inter-lab variability) could be identified. The calibration of the laboratories’ reference counters accounted for most of the variability in the plateau regime, while 20% of the variability was attributed to the sample flow measurement. Differences between soot generators were the main cause of variability in the cut-off regime due to the increased material sensitivity of the CPC at this particle size but had only secondary relevance in the plateau regime. The calibration uncertainty found in this inter-laboratory exercise should be a guideline for users and legislators, as it provides a typical value for the expected measurement uncertainty of a CPC for automotive exhaust PN.

Investigation of the Collected Soot Powder: Thermal Kinetics Analysis, γ-Radiation Treatment, and Clean Environment - Maged Ali Fahmy; Mohamed Raga Balboul; Sameh Mohamed Alyamany (Emission Control Science and Technology, 2021)

A Destruction Mechanism of a Three-Way Catalyst Due to a Failure of Fuel Supply in a Spark Ignition Engine - Andrey V. Porsin; Konstantin V. Bubnov; Yuri A. Moskalets; Givi G. Nadareishvili; Alexey S. Terenchenko; Evgeny A. Alikin; Andrey V. Ushenin (Emission Control Science and Technology, 2021)

Correction to: Development and Validation of a Two-Site Kinetic Model for NH3-SCR over Cu-SSZ-13. Part 2. Full-Scale Model Validation, ASC Model Development, and SCR-ASC Model Application - Rohil Daya; Chintan Desai; Bruce Vernham (Emission Control Science and Technology, 2021)

Spatial Distribution of CO2 Verified Emissions: a Kriging-Based Approach - María Dolores Huete-Morales; Elena Villar-Rubio; Federico Galán-Valdivieso (Emission Control Science and Technology, 2021)

Experimental Investigation of the Effect of Pore Size Distribution on Nano-particle Capture Efficiency Within Ceramic Particulate Filters - Sandeep Viswanathan; Mark L Stewart; David A Rothamer (Emission Control Science and Technology, 2021)

Development of Tire-Wear Particle Emission Measurements for Passenger Vehicles - Yoshio Tonegawa; Sousuke Sasaki (Emission Control Science and Technology, 2021)
In this study, we aimed to develop a new method for measuring tire-wear particles of less than 2.5 μm generated from vehicle use. We also aimed to devise a method for evaluating the emission factor of tire-wear particles. To develop an evaluation method for tire-wear particles, we examined several factors, such as how tire components in airborne particles collected on a sampling filter were measured, the comparison of tire-wear particles obtained in a laboratory study and an on-road study, a method for measuring tire-wear particles using a test vehicle, and a method for evaluating tire-wear mass using a weighting balance. Measurements of tire-wear particles were carried out using the measurement method proposed herein. The amount of tire wear that the particles generated was almost constant in a vehicle speed range of 20–40 km/h but was influenced by a change in lateral acceleration in the range of 0–0.4G. Furthermore, the relationship between the emission of tire-wear particles and the lateral acceleration force can be shown by a quadratic polynomial. We estimated the emission factor of tire-wear particles by applying the relational equation to the speed profile of the JC08 used in Japanese exhaust gas tests. The emission factor of the test tire used in this study was 3.7 mg/km-vehicle. The ratio of the tire-wear particles to tread wear mass was about 3.3% at PM 2.5 and 3.7% at PM 10 .

Application of a Diffusion Charger to Quantify Real-Time Particle Emissions from Light-Duty Vehicles: a Comparison Study with a Particle Size Spectrometer - Heejung Jung; David Quiros; Yang Li; Shaohua Hu; Yue Lin (Emission Control Science and Technology, 2021)

Modeling and Optimization of Multi-functional Ammonia Slip Catalysts for Diesel Exhaust Aftertreatment - Thomas Klint Torp; Brian Brun Hansen; Peter N. R. Vennestrøm; Ton V. W. Janssens; Anker Degn Jensen (Emission Control Science and Technology, 2021)

Lean-Burn Natural Gas Engines: Challenges and Concepts for an Efficient Exhaust Gas Aftertreatment System - Patrick Lott; Olaf Deutschmann (Emission Control Science and Technology, 2021)
High engine efficiency, comparably low pollutant emissions, and advantageous carbon dioxide emissions make lean-burn natural gas engines an attractive alternative compared to conventional diesel or gasoline engines. However, incomplete combustion in natural gas engines results in emission of small amounts of methane, which has a strong global warming potential and consequently makes an efficient exhaust gas aftertreatment system imperative. Palladium-based catalysts are considered as most effective in low temperature methane conversion, but they suffer from inhibition by the combustion product water and from poisoning by sulfur species that are typically present in the gas stream. Rational design of the catalytic converter combined with recent advances in catalyst operation and process control, particularly short rich periods for catalyst regeneration, allow optimism that these hurdles can be overcome. The availability of a durable and highly efficient exhaust gas aftertreatment system can promote the widespread use of lean-burn natural gas engines, which could be a key step towards reducing mankind’s carbon footprint.

Correction to: Effect of Copper Loading in Copper-Alumina Aerogels on Three-Way Catalytic Performance - Ann M. Anderson; Bradford A. Bruno; Frank Dilone; Matthew T. LaRosa; Thomas F. Andre; Chris Avanessian; Mary K. Carroll (Emission Control Science and Technology, 2020)

Unexpected Low-Temperature deNOx Activity of AdSCR Systems for Cold Start NOx Abatement - Federica Gramigni; Nicole Daniela Nasello; Tommaso Selleri; Isabella Nova; Enrico Tronconi; Simone Dieterich; Michel Weibel (Emission Control Science and Technology, 2020)

The Reactions and Role of Ammonia Slip Catalysts in Modern Urea-SCR Systems - T. Maunula; M. Tuikka; T. Wolff (Emission Control Science and Technology, 2020)

Chemical Kinetics Modeling and Analysis of Monomethylamine for Power Plants Selective Non-Catalytic Reduction (SNCR) Systems - Carlos E. Romero; Nasser Vahedi; Yan Qin (Emission Control Science and Technology, 2020)

Performance of a Diesel Particle Filter Damaged by Drilling Holes in the Filter Walls to Simulate Internal Micro-cracks - Denis Bémer; Dominique Thomas; Stéphanie Pacault (Emission Control Science and Technology, 2020)

Significance of Oxygen Storage Capacity of Catalytic Materials in Emission Control Application - Deboshree Mukherjee; Benjaram M. Reddy (Emission Control Science and Technology, 2020)

SCR-Filter Model Order Reduction (2): Proper Orthogonal Decomposition and Artificial Neural Network - Seun Olowojebutu; Thomas Steffen; Phillip Bush (Emission Control Science and Technology, 2020)
Catalysed diesel particulate filters (DPF) have been described as multifunctional reactor systems. Integration of selective catalytic reduction (SCR) functionality in the DPF creates an SCR-in-DPF system that achieves nitrous oxides (NO x ) treatment along with particulate matter (PM) collection. The physical and chemical aspects of the integrated SCR-filter complicate system modelling. The goal of this work is to develop low-complexity model of the SCR-filter system which retains high fidelity. A high-fidelity model of the SCR-coated filter has been developed and validated. The performance of the model was described in a previous paper. Model complexity reduction is attempted in this paper. The objective is to achieve simulation times that can support the deployment of the model for online system control in an engine control unit. Two approaches were taken for the SCR-coated filter model order reduction (MOR): a “grey-box” approach via proper orthogonal decomposition (POD) and a “black box” approach via artificial neural network (ANN) function approximation. The POD method is shown to deliver a significant MOR while maintaining a high degree of fidelity but with less than 5% improvement in simulation time. The ANN method delivers a substantial MOR with reduction of three orders of magnitude in simulation time. The accuracy of the ANN model is satisfactory with good generalisation to new test data but noticeably inferior to the POD method.

Catalytic Paper Filters for Diesel Soot Abatement: Studies at Laboratory and Bench Scales - Nicolás Sacco; Ezequiel Banús; Viviana Milt; Eduardo Miró; Juan Pablo Bortolozzi (Emission Control Science and Technology, 2020)

Changes in Total Friction in the Engine, Friction in Timing Chain Transmissions and Engine Emissions Due to Adding TiO2 Nanoparticles to Engine Oil - M. Wozniak; D. Batory; K. Siczek; G. Ozuna (Emission Control Science and Technology, 2020)
The main aim of the study was to evaluate changes in total friction in the engine, friction in its timing chain transmissions and engine emissions resulting from adding TiO 2 nanoparticles to engine oil. The applicable engine oils and factors affecting their features were discussed. The drive from the crankshaft to the camshaft in an internal combustion engine is usually carried out by means of a cogged belt transmission or a chain transmission when high mileage is required without service operations. The engine performance of analyzed SI engine was obtained from the literature. The dependency of engine emission on engine operating speed was obtained using data from tests of a very similar engine under standard test conditions described in the literature. The changes in engine characteristics caused by varying internal friction conditions were estimated using the engine performance characteristic and engine friction losses, particularly in valve train chain transmission. The friction in such a chain transmission operating under oil lubrication conditions can be determined using its analytical model and measured friction torque occurring between the chain rollers and the pins. The analytical model was developed using the finite element method and additional mathematical formulas. The proposed model allowed obtaining weight and mass inertial moments of all valve train transmission components. The friction torque in contact zone chain roller–pin was obtained using the elaborated physical pendulum method for different conditions of lubrication, namely, without oil, with pure engine oil, and with engine oil containing TiO 2 nanoparticles. The engine oil SAE 10W-40 with/without dispersed 2% wt. TiO 2 nanoparticles was used during tests. The preparation process of studied oils was described. The resulted values of the friction torque in the chain transmission operating in different conditions of lubrication and changes in engine emission have been presented for tests before and after addition of TiO2 nanoparticles into engine oil. During the measurements it was observed that the addition of 2% TiO2 nanoparticles into engine oil reduced the total friction losses by 7–7.7%. Additionally, it was demonstrated that the timing drive and valve train generate about 14.4–18% of overall engine friction losses. Based on the results obtained from a comparative analysis of emission in the other engine with similar power characteristics, the mentioned total friction losses can change the emission of the following compounds in the analyzed SI engine: 17–19% for CO, 8–9% for CO 2 , 13–17% for NO x , and 12–16% for HC. Such changes were dependent on the engine speed. The smallest changes in engine were registered for the rotation speed of 2500 rpm. The oil consumption in the engine and its impact on the PM emission was estimated. The additional arrangements facilitating the extrapolation of the obtained friction results to the cases of using other oils and the method of measuring the PM emission on the test stand were proposed.

Nonuniform Oxidation Behavior of Loaded Gasoline Particulate Filters - Melanie Moses-DeBusk; John M.E. Storey; Mary A. Eibl; John F. Thomas; Todd J. Toops; Charles E.A. Finney; Josh A. Pihl; Hassina Z. Bilheux; Jens Gregor (Emission Control Science and Technology, 2020)
The results of an experimental study on the oxidation behavior of loaded gasoline particulate filters (GPFs) from a gasoline direct injection (GDI) engine are reported. PM was loaded on uncatalyzed cordierite GPF mini-cores by exposure to exhaust from a light-duty GDI engine operating during a rich acceleration condition on four fuels: 100% gasoline (E0); a 30% blend of ethanol in gasoline (E30); a 24% blend of isobutanol in gasoline (iBu24); or a 48% blend of isobutanol in gasoline (iBu48). The oxidative reactivities of these four types of PM were investigated as a function of temperature. Compared with E0, particulate matter (PM) from the ethanol blend showed a significant shift to lower temperature activity, whereas both isobutanol blends produced PM requiring higher temperatures to achieve complete oxidation. The oxidation kinetics of the E0 and E30 PM were studied in more detail. These cores were used in pulsed-oxidation studies to explore the oxidation kinetics of the PM throughout a stepwise burnout (i.e., regeneration). The results suggest that the reactivity of PM on GPF cores is sensitive to both its environmental history and the type of fuel being used. A unique neutron-imaging study was also performed on E0 and E30-loaded GPF cores to study how the PM layer thicknesses change during a stepwise burnout.

Evaluation of Catalysts Derived from Palm Kernel Shell Carbon in a Passive NOx Removal from a Diesel Engine Exhaust - Tan Yong Chin; Ibrahim Yakub; Taufiq-Yap Yun Hin (Emission Control Science and Technology, 2020)

Effect of Copper Loading in Copper-Alumina Aerogels on Three-Way Catalytic Performance - Ann M. Anderson; Braford A. Bruno; Frank Dilone; Matthew T. LaRosa; Thomas F. Andre; Chris Avanessian; Mary K. Carroll (Emission Control Science and Technology, 2020)

Nanoarray-Based Monolithic Adsorbers for SO2 Removal - Junfei Weng; Pu-Xian Gao; Zhiming Gao; Josh Pihl; Tim LaClair; Mingkan Zhang; Kyle Gluesenkamp; Ayyoub Momen (Emission Control Science and Technology, 2020)

Experimental Assessment of Effects of n-Butanol on Performance, Emission, and Combustion Characteristics of Mahua Oil Fueled Reactivity Controlled Compression Ignition (RCCI) Engine - Nataraj Ganesan; Senthilkumar Masimalai; Porpatham Ekambaram; Karthic Selvaraju (Emission Control Science and Technology, 2020)

Static Cooling of a Monolith Converter: Influence of Radiation and Natural Convection - Joseph P. Mmbaga; Andres Donoso-Bravo; Robert E. Hayes (Emission Control Science and Technology, 2020)

Simulation of Flow Patterns in Particulate Filters with Various Viscous Models - Ileana M. Vega Mesquida; Ivan Cornejo; Petr Nikrityuk; Robert E. Hayes (Emission Control Science and Technology, 2020)

Impacts of Exhaust Transfer System Contamination on Particulate Matter Measurements - Jiacheng Yang; Liem Pham; Kent C. Johnson; Thomas D. Durbin; Georgios Karavalakis; David Kittelson; Heejung Jung (Emission Control Science and Technology, 2020)

Numerical Investigation of NOx Emission Reduction in Non-Premixed Lean Reverse-Flow Combustor in a Micro Gas Turbine Engine - Jesline Joy; Peng Cheng Wang; Jeggathishwaran Panisilvam; Simon Ching Man Yu (Emission Control Science and Technology, 2020)

A Holistic View on Urea Injection for NOx Emission Control: Impingement, Re-atomization, and Deposit Formation - J. Dörnhöfer; M. Börnhorst; C. Ates; N. Samkhaniani; J. Pfeil; M. Wörner; R. Koch; H.-J. Bauer; O. Deutschmann; B. Frohnapfel; T. Koch (Emission Control Science and Technology, 2020)

Deposit Formation from Urea Injection: a Comprehensive Modeling Approach - U. Budziankou; M. Börnhorst; C. Kuntz; O. Deutschmann; T. Lauer (Emission Control Science and Technology, 2020)
Long-term reliability is one of the major requirements for automotive exhaust aftertreatment systems with selective catalytic reduction (SCR) using urea water solution (UWS) as NH 3 carrier fluid. A high injection rate of UWS or unfavorable operating conditions may lead to formation of solid deposits, which decrease system efficiency by increasing backpressure and impairing ammonia uniformity. A reliable numerical prediction of deposit formation in urea SCR systems is desired for optimization of system design. However, comprehensive modeling of physical and chemical processes in the tailpipe as well as different time scale phenomena represents a challenging task. This study presents a comprehensive approach for modeling UWS injection, droplet impingement, liquid film and deposit formation based on CFD-simulation. An existing kinetic model for urea decomposition is integrated into the CFD code to predict solid by-product formation from wall films. Physical simulation time is extensively increased by substituting the Lagrange-particles with source terms of mass, momentum and energy reducing simulation time by a factor of 20. The comparison of measured and simulated results shows the capability of the presented modeling approach to predict position and chemical composition of solid deposits.

Performance of Broken Particulate Filters—a 1D and 3D Simulation Study - T. Chittipotula; S. Kutschi; J. C. Wurzenberger (Emission Control Science and Technology, 2020)

Approaches for a New Generation of Fast-Computing Catalyst Models - Christian März; Johannes Werfel; Joana Kühne; Robert Scholz (Emission Control Science and Technology, 2020)

Hybrid FEM and FDM Approach for Monolithic Catalytic Converters with Pore Diffusion - Wen Wang; Edward J. Bissett; Syed Wahiduzzaman (Emission Control Science and Technology, 2020)

Understanding Factors Affecting the Balance Point (and Rate of Balance Point Approach) of a Diesel Particulate Filter: an Analytical Expression for the Balance Point Soot Loading - Timothy C. Watling (Emission Control Science and Technology, 2020)

Kinetic Modelling of Co3O4- and Pd/Co3O4-Catalyzed Wet Lean Methane Combustion - Somaye Nasr; Natalia Semagina; Robert E. Hayes (Emission Control Science and Technology, 2020)

Impact of Lubricant Oil Additives on the Performance of Pd-Based Three-Way Catalysts - Daekun Kim; Todd J. Toops; Ke Nguyen; D. William Brookshear; Michael J. Lance; Jun Qu (Emission Control Science and Technology, 2020)

Palladium/Zeolite Low Temperature Passive NOx Adsorbers (PNA): Structure-Adsorption Property Relationships for Hydrothermally Aged PNA Materials - Konstantin Khivantsev; Nicholas R. Jaegers; Libor Kovarik; Jian Zhi Hu; Feng Gao; Yong Wang; János Szanyi (Emission Control Science and Technology, 2020)

A Review of the 2018 U.S.-DOE CLEERS Conference: Trends and Deeper Insights in Reduction of NOx and Particulate in Diesel and Gasoline Engines and Advances in Catalyst Materials, Mechanisms, and Emission Control Technologies - M. Masoudi; J. Hensel; E. Tegeler (Emission Control Science and Technology, 2020)

Design of a Novel Gasoline Particulate Filter Aging Method - Stefan Sterlepper; Johannes Claßen; Stefan Pischinger; Jim Cox; Michael Görgen; Helmut Lehn; Johannes Scharf (Emission Control Science and Technology, 2020)

Effect of Additives to Improve Calcium-Based Sorbents in Semi-Dry Flue Gas Desulphurization - Ítalo W. L. França; Samuel J. M. Cartaxo; Moises Bastos-Neto; Luciana R. B. Gonçalves; Fabiano A. N. Fernandes (Emission Control Science and Technology, 2020)

A Laboratory Study of Low-Temperature CO Removal from Mobile Exhaust Gas Using In-Plasma Catalysis - Rasoul Yarahmadi; Somayeh Soleimani-Alyar (Emission Control Science and Technology, 2020)

SCR-Filter Model Order Reduction (1): Development and Validation of the Base “High-Fidelity” Model - Seun Olowojebutu; Thomas Steffen; Phillip Bush (Emission Control Science and Technology, 2020)
Catalysed diesel particulate filters (c-DPF) have been described as multifunctional reactor systems. Integration of selective catalytic reduction (SCR) functionality in the DPF enhances filter performance to achieve nitrous oxides (NO x ) treatment along with particulate matter (PM) collection. The physical and chemical aspects of the integrated SCR-filter make modelling difficult. The goal of this work is to develop a low-complexity model of the SCR-filter system with good fidelity. The first part of our work—presented in this paper—lays out the structure of the SCR-filter model and highlights a new approach to implement faster than real-time solution to the “full-order” or “high-complexity” model. The validated model was applied to evaluate the impact of diffusion on deNOx functionality of the SCR-filter system in a simulated characterisation exercise for the SCR-filter unit. We found that internal (pore) diffusion (effective diffusivity coefficient) and external channel to wall diffusion (mass transfer coefficient) orthogonal to the channel direction are significant for accurate characterisation of the deNOx performance of the SCR-coated filter system. System modelling can be used to select the geometric properties of the monolith (length and density of the SCR-coated filter system) and micro-properties of the washcoat (catalyst loading and zoning) to optimise the influence of diffusion on the system performance. The main contribution of this paper is the presentation of a different approach to implementing the solution to the cDPF model and in enough detail so that it can be easily replicated.

Characterization of the Miniaturized Inverted Flame Burner as a Combustion Source to Generate a Nanoparticle Calibration Aerosol - Oliver F. Bischof; Patrick Weber; Ulrich Bundke; Andreas Petzold; Astrid Kiendler-Scharr (Emission Control Science and Technology, 2020)

Diesel Particulate Filter Cleaning Effectiveness: Estimated Ash Loading, Quantified Particulate Removal, and Post-cleaning Filter Pressure Drop - John T. Fox; Kun Yang; Robert Hunsicker (Emission Control Science and Technology, 2020)

Assessment of the Single-Site Kinetic Model for NH3-SCR on Cu-Chabazite for the Prediction of NOx Emissions in Dynamometer Tests - Selmi Erim Bozbağ; Mutlu Şimşek; Onur Demir; Deniz Şanlı; Barkın Ozener; Gokhan Hisar; Can Erkey (Emission Control Science and Technology, 2020)

A Two-Stage Model for Sequential Engine-Out and Tailpipe Emission Estimation - Roland Schmid; Johannes Bürger; Jia Chen (Emission Control Science and Technology, 2020)

Development of Reduction Scenarios Based on Urban Emission Estimation and Dispersion of Exhaust Pollutants from Light Duty Public Transport: Case of Tabriz, Iran - Mina Jamshidi Kalajahi; Leila Khazini; Yousef Rashidi; Saeed Zeinali Heris (Emission Control Science and Technology, 2020)

TiO2 Coated-Asphalt Buton Photocatalyst for High-Performance Motor Vehicles Gas Emission Mitigation - Muhammad Zakir Muzakkar; Muhammad Nurdin; Ima Ismail; Maulidiyah Maulidiyah; Dwiprayogo Wibowo; Ratna Ratna; Siti Khatijah Md Saad; Akrajas Ali Umar (Emission Control Science and Technology, 2020)

Preface to Special Issue - Benjaram M. Reddy; Martin Muhler (Emission Control Science and Technology, 2019)

Studies on the Solid Oxide Cell Perovskite Electrode Materials for Soot Oxidation Activity - Chaitra S. Shenoy; Sunaina S. Patil; P. Govardhan; Atmuri Shourya; Hari Prasad Dasari; M. B. Saidutta; Harshini Dasari (Emission Control Science and Technology, 2019)

Nature and Surface Interactions of Sulfur-Containing Deposits on V2O5-WO3/TiO2 Catalysts for SCR-DeNOx - Thomas Rammelt; Agnieszka-Beata Kuc; Jürgen Böhm; Thomas Heine; Roger Gläser (Emission Control Science and Technology, 2019)

Design of a Reactor Cell for Modulated Excitation Raman and Diffuse Reflectance Studies of Selective Catalytic Reduction Catalysts - Rob Jeremiah G. Nuguid; Davide Ferri; Oliver Kröcher (Emission Control Science and Technology, 2019)

Effect of the NH4NO3 Addition on the Low-T NH3-SCR Performances of Individual and Combined Fe- and Cu-Zeolite Catalysts - R. Villamaina; I. Nova; E. Tronconi; T. Maunula; M. Keenan (Emission Control Science and Technology, 2019)
We have measured NOx conversions and N 2 O productions over Fe-BEA and Cu-SAPO catalysts and over their sequential arrangements under Enhanced SCR conditions, resulting from the addition of an aqueous solution of ammonium nitrate (AN) to the typical Standard SCR feed stream, and we have compared them to those observed under Standard and Fast SCR conditions. The expected strong enhancement of the poor low temperature activity of the Fe-BEA catalyst was confirmed: both NH 3 and NOx conversions and N 2 O formations similar to those of the Fast SCR reaction were achieved when cofeeding ammonium nitrate. On the other hand, the Cu-SAPO efficiency was drastically decreased by the addition of AN at low temperatures, possibly due to trapping of the ammonium nitrate salt within the SAPO zeolite, characterized by smaller pores than those of the BEA zeolite. The Cu-SAPO performances were recovered only at T > 250 °C with a huge release of N 2 O due to the thermal decomposition of AN. The combined system with the Fe-zeolite sample placed upstream of the Cu-zeolite also exhibited outstanding low temperature deNOx performances, with even lower N 2 O production than over the Fe-zeolite only at the same Enhanced SCR (E-SCR) conditions.

CuO/Zn-CeO2 Nanocomposite as an Efficient Catalyst for Enhanced Diesel Soot Oxidation - Perala Venkataswamy; Deshetti Jampaiah; Deboshree Mukherjee; Benjaram M. Reddy (Emission Control Science and Technology, 2019)

Laser Raman Spectroscopic Investigation on the Conversion of Molten Urea into NH3 for the Selective Catalytic Reduction of NOx in Oxygen-Rich Exhaust Gases - Philipp Langenfeld; Christoph Hahn; Andreas Roppertz; Sven Kureti (Emission Control Science and Technology, 2019)

Synthesis and Study of Bimetallic Pd-Rh System Supported on Zirconia-Doped Alumina as a Component of Three-way Catalysts - Aleksey A. Vedyagin; Roman M. Kenzhin; Mikhail Yu. Tashlanov; Vladimir O. Stoyanovskii; Pavel E. Plyusnin; Yury V. Shubin; Ilya V. Mishakov; Alexander V. Kalinkin; Mikhail Yu. Smirnov; Valerii I. Bukhtiyarov (Emission Control Science and Technology, 2019)

Catalytic Carbon Monoxide Oxidation over Potassium-Doped Manganese Dioxide Nanoparticles Synthesized by Spray Drying - Kevin Ollegott; Niklas Peters; Hendrik Antoni; Martin Muhler (Emission Control Science and Technology, 2019)

Three-way Catalysis with Noble Metal-Substituted La(Fe,Co)O3 Perovskites—the Role of Noble and Base Metal Components - Sascha Heikens; Viktor Ulrich; Pragati S. Joshi; Bilge Saruhan-Brings; Wolfgang Grünert (Emission Control Science and Technology, 2019)

Passive SCR Performance Under Pseudo-Transient Cycle: Challenges and Opportunities for Meeting Tier 3 Emissions - Vitaly Y. Prikhodko; Josh A. Pihl; Todd J. Toops; James E. Parks (Emission Control Science and Technology, 2019)

A New Periodic Technical Inspection for Particle Emissions of Vehicles - H. Burtscher; Th. Lutz; A. Mayer (Emission Control Science and Technology, 2019)

Selective Catalytic Reduction of NOx over V2O5-WO3-TiO2 SCR Catalysts—A Study at Elevated Pressure for Maritime Pre-turbine SCR Configuration - Steen R. Christensen; Brian B. Hansen; Kim H. Pedersen; Joakim R. Thøgersen; Anker D. Jensen (Emission Control Science and Technology, 2019)

Model-Based Analysis of TWC-Coated Filters Performance - M. A. Mitsouridis; D. Karamitros; G. Koltsakis (Emission Control Science and Technology, 2019)

Impacts of Air-Fuel Stratification in ACI Combustion on Particulate Matter and Gaseous Emissions - Melanie Moses-DeBusk; Scott J. Curran; Samuel A. Lewis; R. Maggie Connatser; John M. E. Storey (Emission Control Science and Technology, 2019)

Effect of Reductants on the NOx Storage Performance of a Pd/CZO Low Temperature NOx Adsorber - Joseph R. Theis; Christine K. Lambert (Emission Control Science and Technology, 2019)

Aftertreatment Protocols for Catalyst Characterization and Performance Evaluation: Low-Temperature Oxidation, Storage, Three-Way, and NH3-SCR Catalyst Test Protocols - Kenneth G. Rappé; Craig DiMaggio; Josh A. Pihl; Joseph R. Theis; Se H. Oh; Galen B. Fisher; Jim Parks; Vencon G. Easterling; Ming Yang; Mark L. Stewart; Kenneth C. Howden (Emission Control Science and Technology, 2019)

Oxidative Reactivity of Particulate Samples from Different Diesel Combustion Systems and Its Relation to Structural and Spectral Characteristics of Soot - Alexandra Zygogianni; Maria Syrigou; Athanasios G. Konstandopoulos; Margaritis Kostoglou (Emission Control Science and Technology, 2019)

Comparison of NOx Adsorption/Desorption Behaviors over Pd/CeO2 and Pd/SSZ-13 as Passive NOx Adsorbers for Cold Start Application - Yongwoo Kim; Sungha Hwang; Jaeha Lee; YoungSeok Ryou; Hyokyoung Lee; Chang Hwan Kim; Do Heui Kim (Emission Control Science and Technology, 2019)

Development of a 2D Model of a SCR Catalyst on a DPF - Venkata R. Chundru; Boopathi S. Mahadevan; John H. Johnson; Gordon G. Parker; Mahdi Shahbakhti (Emission Control Science and Technology, 2019)

Cu Loading Dependence of Fast NH3-SCR on Cu/SSZ-13 - Yanran Cui; Feng Gao (Emission Control Science and Technology, 2019)

Publisher Correction: Difference in the Tailpipe Particle Number by Consideration of Sub-23-nm Particles for Different Injection Settings of a GDI Engine - P. Schwanzer; H.-P. Rabl; S. Loders; P. Seifert; S. Himmelstoß; M. Gaderer (Emission Control Science and Technology, 2019)

Difference in the Tailpipe Particle Number by Consideration of Sub-23-nm Particles for Different Injection Settings of a GDI Engine - P. Schwanzer; H.-P. Rabl; S. Loders; P. Seifert; S. Himmelstoß; M. Gaderer (Emission Control Science and Technology, 2019)

Pressure Response during Filtration and Oxidation in Diesel Particulate Filter - Kazuhiro Yamamoto; Hiroya Kato; Daisuke Suzuki (Emission Control Science and Technology, 2019)

An Asymptotic Solution for Washcoat Pore Diffusion in Catalytic Monoliths: Reformulation and Extension to Small Concentrations - Edward J. Bissett (Emission Control Science and Technology, 2019)

Improving Methodology of Particulate Measurement in Periodic Technical Inspection with High-Sensitivity Techniques: Laser Light Scattering Photometry and Particle Number Method - Hiroyuki Yamada (Emission Control Science and Technology, 2019)

Trends in Automotive Emission Legislation: Impact on LD Engine Development, Fuels, Lubricants and Test Methods: a Global View, with a Focus on WLTP and RDE Regulations - Piotr Bielaczyc; Joseph Woodburn (Emission Control Science and Technology, 2019)

Applied Catalysis in the Automotive Industry: Development of a Commercial Diesel Oxidation Catalyst Simulation Model Balanced for the Requirements of an Original Engine Manufacturer. Part 2, CO and HC Chemistry - Fredrik Blomgren; Soran Shwan; Lars Carlhammar; Staffan Luong; Lennart Andersson; Miroslawa Milh (Emission Control Science and Technology, 2019)

Applied Catalysis in the Automotive Industry: Development of a Commercial Diesel Oxidation Catalyst Simulation Model Balanced for the Requirements of an Original Engine Manufacturer. Part 1, NOx Chemistry - Fredrik Blomgren; Soran Shwan; Lars Carlhammar; Miroslawa Milh (Emission Control Science and Technology, 2019)

What Is the Exposome and How It Can Help Research on Air Pollution - Paolo Vineis (Emission Control Science and Technology, 2019)

Conference Report: 22nd ETH Conference on Combustion Generated Nanoparticles - Hannu E. Jääskeläinen; W. Addy Majewski (Emission Control Science and Technology, 2019)

Study of Brake Wear Particle Emissions of a Minivan on a Chassis Dynamometer - Leonidas Chasapidis; Theodoros Grigoratos; Alexandra Zygogianni; Apostolos Tsakis; Athanasios G. Konstandopoulos (Emission Control Science and Technology, 2018)

A Tutorial on Testing Particulate Filters with a Side-Stream Reactor (SSR) Exhaust Setup - Dimitrios Zarvalis; Leonidas Chasapidis; Ioannis Dolios; Marina Chrysikopoulou; Athanasios G. Konstandopoulos (Emission Control Science and Technology, 2018)

On the Effective Density and Fractal–Like Dimension of Diesel Soot Aggregates as a Function of Mobility Diameter - Penelope Baltzopoulou; Margaritis Kostoglou; Eleni Papaioannou; Athanasios G. Konstandopoulos (Emission Control Science and Technology, 2018)

Dust Filtration Influence on the Performance of Catalytic Filters for NOx Reduction - Giovanny Mateus; Martin Meiller; Karel Soukup; Andreas Hornung (Emission Control Science and Technology, 2018)

Evaluation of Greenhouse Gas Emission Benefits of Vehicle Speed Limiters on On-Road Heavy-Duty Line-Haul Vehicles - Phuong Ho; David Quiros; William Robertson; Chris Ruehl; Wayne Sobieralski; Robert Ianni; Donald Chernich; Renee Littaua (Emission Control Science and Technology, 2018)

Gasoline Particulate Filters—a Review - Ameya Joshi; Timothy V. Johnson (Emission Control Science and Technology, 2018)

Evaluation of Partial Flow Dilution Systems for Very Low PM Mass Measurements - Liem Pham; Jiacheng Yang; Kent Johnson; Thomas Durbin; Georgios Karavalakis; Wayne Miller; David Kittelson; Heejung S. Jung (Emission Control Science and Technology, 2018)

Numerical Investigation of the Effect of Hydrogen Addition on Methane Flame Velocity and Pollutant Emissions Using Several Detailed Reaction Mechanisms - Meryem Alaya; Ridha Ennetta; Rachid Said (Emission Control Science and Technology, 2018)

Coating Distribution in a Commercial SCR Filter - Mark L. Stewart; Carl Justin Kamp; Feng Gao; Yilin Wang; Mark H. Engelhard (Emission Control Science and Technology, 2018)

SO2 Oxidation Across Marine V2O5-WO3-TiO2 SCR Catalysts: a Study at Elevated Pressure for Preturbine SCR Configuration - Steen R. Christensen; Brian B. Hansen; Keld Johansen; Kim H. Pedersen; Joakim R. Thøgersen; Anker Degn Jensen (Emission Control Science and Technology, 2018)

2017 DOE-Crosscut Lean/Low-Temperature Exhaust Emissions Reduction Simulation (CLEERS) Workshop - Todd J. Toops; Vitaly Y. Prikhodko; Josh A. Pihl (Emission Control Science and Technology, 2018)

Development and Validation of a Two-Site Kinetic Model for NH3-SCR over Cu-SSZ-13. Part 1. Detailed Global Kinetics Development Based on Mechanistic Considerations - Rohil Daya; Chintan Desai; Bruce Vernham (Emission Control Science and Technology, 2018)

Development and Validation of a Two-Site Kinetic Model for NH3-SCR over Cu-SSZ-13. Part 2. Full-Scale Model Validation, ASC Model Development, and SCR-ASC Model Application - Rohil Daya; Chintan Desai; Bruce Vernham (Emission Control Science and Technology, 2018)

Frictional and Heat Transfer Characteristics of Flow in Triangle and Hexagon Channels of Wall-Flow Monoliths - Wen Wang; Edward J. Bissett (Emission Control Science and Technology, 2018)

Sensitivity of Three-Way Catalyst Light-Off Temperature to Air-Fuel Ratio - Andrew Bean Getsoian; Joseph R. Theis; Christine K. Lambert (Emission Control Science and Technology, 2018)

Status of Emission Control Science and Technology in Argentina - Julio E. Vassallo (Emission Control Science and Technology, 2018)

A Summary of Sulfur Deactivation, Desorption, and Regeneration Characteristics of Mono- and Bimetallic Pd-Pt Methane Oxidation Catalysts: Pd:Pt Mole Ratio and Particle Size Dependency - Monique Shauntá Wilburn; William S. Epling (Emission Control Science and Technology, 2018)

Comparison of Full Flow Dilution, Partial Flow Dilution, and Raw Exhaust Particle Number Measurements - M. Yusuf Khan; Sagar Sharma; Chet Mun Liew; Abhay Joshi; Daniel Barnes; Nathan Scott; Benjamin Mensen; Tanfeng Cao; Yang Li; Shirish A. Shimpi; Montajir Rahman (Emission Control Science and Technology, 2018)

Efficient Solution of Washcoat Diffusion-Reaction Problem for Real-Time Simulations - Santhosh R. Gundlapally; Ryan Dudgeon; Syed Wahiduzzaman (Emission Control Science and Technology, 2018)

The Development and Application of an Evolutionary Algorithm for the Determination of Kinetic Parameters in Automotive Aftertreatment Models - A. Pedlow; G. McCullough; A. Goguet; O. Garcia-Afonso; D. Sellick (Emission Control Science and Technology, 2018)

Status of Emission Control Science and Technology in South Korea - Chang Hwan Kim; Hyun Sik Han (Emission Control Science and Technology, 2018)

Geometrical Optimization of the Flue Gas Path with Regard to the Reduction of Particulate Matter - Katarina Sulovcova; Radovan Nosek; Jozef Jandacka; Michal Holubcik (Emission Control Science and Technology, 2018)

Predicting Dispersion and Pollutant Concentration of Dimethyl Sulfide (DMS) from a Biofilter Under Various Atmospheric Conditions - Nada Azlah; Zarook Shareefdeen; Ali Elkamel (Emission Control Science and Technology, 2018)

Particulate Matter Production of Small Heat Source Depending on the Bark Content in Wood Pellets - Michal Holubcik; Jozef Jandacka; Radovan Nosek; Jacek Baranski (Emission Control Science and Technology, 2018)

Simultaneous Application of Exhaust Gas Recirculation and Non-Constant Injection Rates to Reduce NOx and Soot Emissions in Diesel Engines - M. Bagheri; R. Baar (Emission Control Science and Technology, 2018)

Biofuel Impact on Diesel Engine After-Treatment: Deactivation Mechanisms and Soot Reactivity - E. Iojoiu; V. Lauga; J. Abboud; G. Legros; J. Bonnety; P. Da Costa; J. Schobing; A. Brillard; G. Leyssens; V. Tschamber; P. Anguita; J. G. Vargas; et al. (Emission Control Science and Technology, 2018)

An Experimental Investigation into the Effect of NO2 and Temperature on the Passive Oxidation and Active Regeneration of Particulate Matter in a Diesel Particulate Filter - Krishnan Raghavan; John Johnson; Jeffrey Naber (Emission Control Science and Technology, 2018)

Nitric Oxide Reduction of Heavy-Duty Diesel Off-Gas by NH3-SCR in Front of the Turbocharger - T. Rammelt; B. Torkashvand; C. Hauck; J. Böhm; R. Gläser; O. Deutschmann (Emission Control Science and Technology, 2017)

Modeling of Exhaust-Gas After-Treatment - Olaf Deutschmann; Daniel Chatterjee (Emission Control Science and Technology, 2017)

The Effect of Evaporation Models on Urea Decomposition from Urea-Water-Solution Droplets in SCR Conditions - Marcus Stein; Viatcheslav Bykov; Ulrich Maas (Emission Control Science and Technology, 2017)

CFD Simulation of Liquid Back Suction and Gas Bubble Formation in a Circular Tube with Sudden or Gradual Expansion - Xuan Cai; Martin Wörner; Holger Marschall; Olaf Deutschmann (Emission Control Science and Technology, 2017)

Model-Based Optimization of Ammonia Dosing in NH3-SCR of NO x for Transient Driving Cycle: Model Development and Simulation - Sivaram Kannepalli; Adrian Bürger; Steffen Tischer; Olaf Deutschmann (Emission Control Science and Technology, 2017)

Application of Surrogate Modelling to the Optimisation of Kinetic Parameters in an Emissions Control Catalyst Model Using Vehicle Drive Cycle Data - Jonathan E. Etheridge; Gareth John; Timothy C. Watling (Emission Control Science and Technology, 2017)

Turbulence Decay Inside the Channels of an Automotive Catalytic Converter Monolith - I. Cornejo; P. Nikrityuk; R. E. Hayes (Emission Control Science and Technology, 2017)

Selective Non-catalytic Reduction (SNCR) of CO2 and NO Emissions from a Single-Cylinder CI Engine Using Chemical Absorbents - S. Thiyagarajan; V. Edwin Geo; Leenus Jesu Martin; B. Nagalingam (Emission Control Science and Technology, 2017)

World Medical Association’s Concern Regarding Effects of Ultrafine Particles and Vehicular Emissions: Report from 65th General Assembly in Durban, South Africa - Heinz Fuchsig; Manfred Neuberger (Emission Control Science and Technology, 2017)

Impact of Rapid Cycling Strategy on Reductant Effectiveness During NO x Storage and Reduction - Mengmeng Li; Yang Zheng; Dan Luss; Michael P. Harold (Emission Control Science and Technology, 2017)

Anthropogenic Carbon Nanotubes and Air Pollution - Jelena Kolosnjaj-Tabi; Fathi Moussa (Emission Control Science and Technology, 2017)

Erratum to: Impact of Emerging Engine and After-Treatment Technologies for Improved Fuel Efficiency and Emission Reduction for the Future Rail Diesel Engines - Carlo Beatrice; Natale Rispoli; Gabriele Di Blasio; Athanasios G. Konstandopoulos; Eleni Papaioannou; Abdurrahman Imren (Emission Control Science and Technology, 2017)

Catalytic Conversion of CO2 to CH4 with a Ru Catalyst: Application at Vehicle Exhaust - F. Murena; M. V. Prati (Emission Control Science and Technology, 2017)

Real-World NO X Emissions of Transit Buses Equipped with Diesel Exhaust Aftertreatment Systems - Andrew J. Kotz; David B. Kittelson; William F. Northrop; Niklas Schmidt (Emission Control Science and Technology, 2017)

Predicting Pressure Drop, Temperature, and Particulate Matter Distribution of a Catalyzed Diesel Particulate Filter Using a Multi-Zone Model Including Cake Permeability - Boopathi S. Mahadevan; John H. Johnson; Mahdi Shahbakhti (Emission Control Science and Technology, 2017)

Particle and VOC Emissions from Stoichiometric Gasoline Direct Injection Vehicles and Correlation Between Particle Number and Mass Emissions - Hiroyuki Yamada; Satoshi Inomata; Hiroshi Tanimoto (Emission Control Science and Technology, 2017)

Erratum to: Biological Effects in Lung Cells In Vitro of Exhaust Aerosols from a Gasoline Passenger Car With and Without Particle Filter - Christoph Bisig; Sandro Steiner; Pierre Comte; Jan Czerwinski; Andreas Mayer; Alke Petri-Fink; Barbara Rothen-Rutishauser (Emission Control Science and Technology, 2017)

Impact of Zeolite Beta on Hydrocarbon Trapping and Light-Off Behavior on Pt/Pd/BEA/Al2O3 Monolith Catalysts - Gregory S. Bugosh; Michael P. Harold (Emission Control Science and Technology, 2017)

Natural Gas Engine Emission Reduction by Catalysts - Kati Lehtoranta; Timo Murtonen; Hannu Vesala; Päivi Koponen; Jenni Alanen; Pauli Simonen; Topi Rönkkö; Hilkka Timonen; Sanna Saarikoski; Teuvo Maunula; Kauko Kallinen; Satu Korhonen (Emission Control Science and Technology, 2017)

Urea-Water-Solution Properties: Density, Viscosity, and Surface Tension in an Under-Saturated Solution - Sauli Halonen; Teija Kangas; Mauri Haataja; Ulla Lassi (Emission Control Science and Technology, 2017)

Gasoline Particle Filter Development - Christine Lambert; Timothy Chanko; Douglas Dobson; Xin Liu; James Pakko (Emission Control Science and Technology, 2017)

A Study of the Soot Combustion Efficiency of an SCRF® Catalyst vs a CSF During Active Regeneration - Lasitha Cumaranatunge; Andrew Chiffey; Joel Stetina; Kevin McGonigle; Griffin Repley; Andrew Lee; Sougato Chatterjee (Emission Control Science and Technology, 2017)

Understanding low temperature oxidation activity of nanoarray-based monolithic catalysts: from performance observation to structural and chemical insights - Shoucheng Du; Wenxiang Tang; Yanbing Guo; Andrew Binder; Eleni A. Kyriakidou; Todd J. Toops; Sibo Wang; Zheng Ren; Son Hoang; Pu-Xian Gao (Emission Control Science and Technology, 2017)

CeO2-M2O3 Passive NO x Adsorbers for Cold Start Applications - Samantha Jones; Yaying Ji; Agustín Bueno-Lopez; Yang Song; Mark Crocker (Emission Control Science and Technology, 2017)

Evaluation of Mn and Sn-Modified Pd-Ce-Based Catalysts for Low-Temperature Diesel Exhaust Oxidation - Chao Wang; Andrew J. Binder; Todd J. Toops; Jochen Lauterbach; Erdem Sasmaz (Emission Control Science and Technology, 2017)

Coupled Heterogeneous and Homogeneous Hydrocarbon Oxidation Reactions in Model Diesel Oxidation Catalysts - Melanie J. Hazlett; William S. Epling (Emission Control Science and Technology, 2017)

Cold-Start Emission Reduction Potential and Limitations of Commercial Passive Hydrocarbon Adsorbers - Michelle H. Wiebenga; Se H. Oh; Gongshin Qi (Emission Control Science and Technology, 2017)

Response Characteristics of Stable Mixed-Potential NH3 Sensors in Diesel Engine Exhaust - Eric L. Brosha; Vitaly Y. Prikhodko; Cortney R. Kreller; Josh A. Pihl; Scott Curran; James E. Parks; R. Mukundan (Emission Control Science and Technology, 2017)

Development of a Global Kinetic Model for a Commercial Lean NOx Trap Automotive Catalyst Based on Laboratory Measurements - Mahsa Rafigh; Ryan Dudgeon; Josh Pihl; Stuart Daw; Richard Blint; Syed Wahiduzzaman (Emission Control Science and Technology, 2017)

A Review of the Annual US-DOE CLEERS Conference: Trends in Real Driving Emissions, Novel Catalyst Technologies, and NOx Reduction - John Hoard (Emission Control Science and Technology, 2017)

Characterization and Evaluation of Methane Oxidation Catalysts for Dual-Fuel Diesel and Natural Gas Engines - Donnie J. Worth; Marc E. J. Stettler; Paul Dickinson; Kieran Hegarty; Adam M. Boies (Emission Control Science and Technology, 2016)

The Advanced Collaborative Emissions Study (ACES) of 2007- and 2010-Emissions Compliant Heavy-Duty Diesel Engines: Characterization of Emissions and Health Effects - Maria G. Costantini; Imad Khalek; Jacob D. McDonald; Annemoon M. van Erp (Emission Control Science and Technology, 2016)

HC-Induced Deactivation in CO Conversion at Diesel Oxidation Catalysts - M. Herrmann; S. Malmberg; A. Drochner; H. Vogel; R. Hayes; M. Votsmeier (Emission Control Science and Technology, 2016)

CFD Evaluation of In Situ Probe Techniques for Catalytic Honeycomb Monoliths - Matthias Hettel; Claudia Antinori; Olaf Deutschmann (Emission Control Science and Technology, 2016)

Real-World Emissions from Modern Heavy-Duty Diesel, Natural Gas, and Hybrid Diesel Trucks Operating Along Major California Freight Corridors - David C. Quiros; Arvind Thiruvengadam; Saroj Pradhan; Marc Besch; Pragalath Thiruvengadam; Berk Demirgok; Daniel Carder; Adewale Oshinuga; Tao Huai; Shaohua Hu (Emission Control Science and Technology, 2016)

Formation of Urea-Based Deposits in an Exhaust System: Numerical Predictions and Experimental Observations on a Hot Gas Test Bench - Wolfgang Brack; Barbara Heine; Felix Birkhold; Matthias Kruse; Olaf Deutschmann (Emission Control Science and Technology, 2016)

Development of ECU Capable Grey-Box Models from Detailed Models—Application to a SCR Reactor - Santhosh R. Gundlapally; Iakovos Papadimitriou; Syed Wahiduzzaman; Tian Gu (Emission Control Science and Technology, 2016)

A Comprehensive Evaluation of a Gaseous Portable Emissions Measurement System with a Mobile Reference Laboratory - Tanfeng Cao; Thomas D. Durbin; David R. Cocker; Roland Wanker; Thomas Schimpl; Volker Pointner; Karl Oberguggenberger; Kent C. Johnson (Emission Control Science and Technology, 2016)

Regulatory Update: CARB Passes USA’s First Regulations for Heavy-Duty Diesel Engine Replacement Filters - Mansour Masoudi (Emission Control Science and Technology, 2016)

Characterizing Diesel Particulate Filter Failure During Commercial Fleet Use due to Pinholes, Melting, Cracking, and Fouling - Kun Yang; John T. Fox; Robert Hunsicker (Emission Control Science and Technology, 2016)

Hysteresis Phenomena on Platinum and Palladium-based Diesel Oxidation Catalysts (DOCs) - H. Dubbe; F. Bühner; G. Eigenberger; U. Nieken (Emission Control Science and Technology, 2016)

TWC Performance of Honeycomb Catalysts Coated with Pd-Supported 10Al2O3 · 2B2O3 and Its Cation-Substituted Compounds - Yuki Nagao; Yunosuke Nakahara; Takahiro Sato; Shuji Nakano; Masato Machida (Emission Control Science and Technology, 2016)

Impact of Emerging Engine and After-Treatment Technologies for Improved Fuel Efficiency and Emission Reduction for the Future Rail Diesel Engines - Carlo Beatrice; Natale Rispoli; Gabriele Di Blasio; Athanasios G. Konstandopoulos; Eleni Papaioannou; Abdurrahman Imren (Emission Control Science and Technology, 2016)

Synthesis of Nickel and Zinc-Doped Aluminogallate Nanocomposite Spinels with the Hydrothermal Method and Wet Atomization for NO Reduction - Md. Hasan Zahir; Shamseldin A. Mohamed; Toshio Suzuki (Emission Control Science and Technology, 2016)

Characterization of Real-Time Particle Emissions from a Gasoline Direct Injection Vehicle Equipped with a Catalyzed Gasoline Particulate Filter During Filter Regeneration - Tak W. Chan; Meghdad Saffaripour; Fengshan Liu; Jill Hendren; Kevin A. Thomson; Joseph Kubsh; Rasto Brezny; Greg Rideout (Emission Control Science and Technology, 2016)

A Generalized Approach for Verifying the Emission Benefits of Off-Road Hybrid Mobile Sources - Varalakshmi Jayaram; M. Yusuf Khan; William A. Welch; Kent Johnson; J. Wayne Miller; David R. Cocker (Emission Control Science and Technology, 2016)

The Relative Contributions of Mobile Sources to Air Pollutant Emissions in Tehran, Iran: an Emission Inventory Approach - Hossein Shahbazi; Masoud Reyhanian; Vahid Hosseini; Hossein Afshin (Emission Control Science and Technology, 2016)

Enhancing the Low-T NH3-SCR Activity of a Commercial Fe-Zeolite Catalyst by NH4NO3 Dosing: an Experimental and Modeling Study - F. Marchitti; E. Barker Hemings; I. Nova; P. Forzatti; E. Tronconi (Emission Control Science and Technology, 2016)

Dynamic Modeling and Analysis of an Industrial Gas Suspension Absorber for Flue Gas Desulfurization - Stefano Cignitti; Seyed Soheil Mansouri; Mauricio Sales-Cruz; Flemming Jensen; Jakob Kjøbsted Huusom (Emission Control Science and Technology, 2016)

Powder Resistivity Inferred Differential Collection of Heterogeneous Coal Fly Ash and Powered Activated Carbon Admixtures Within a Cylindrical Electrostatic Precipitator - Eric Monsu Lee; Herek L. Clack (Emission Control Science and Technology, 2016)

Influence of Supports on Pd Catalysts for the Selective Catalytic Reduction of NOx with H2 and CO - Gianni Caravaggio; Lioudmila Nossova; Raymond Burich (Emission Control Science and Technology, 2016)

The Repeatability and Reproducibility of Particle Number Measurements from a Heavy Duty Diesel Engine - M. Yusuf Khan; Shirish A. Shimpi; William T. Martin (Emission Control Science and Technology, 2015)

Measurement of Vanadium Emissions from SCR Catalysts by ICP-OES: Method Development and First Results - T. J. Schildhauer; M. Elsener; J. Moser; I. Begsteiger; D. Chatterjee; K. Rusch; O. Kröcher (Emission Control Science and Technology, 2015)

Experimental and Simulation Analysis of Temperature and Particulate Matter Distribution for a Catalyzed Diesel Particulate Filter - Boopathi S. Mahadevan; John H. Johnson; Mahdi Shahbakhti (Emission Control Science and Technology, 2015)

Rh Supported on LaPO4/SiO2 Nanocomposites as Thermally Stable Catalysts for TWC Applications - Haris Puspito Buwono; Taishi Eidome; Saki Minami; Satoshi Hinokuma; Yuki Nagao; Yunosuke Nakahara; Masato Machida (Emission Control Science and Technology, 2015)

Biological Effects in Lung Cells In Vitro of Exhaust Aerosols from a Gasoline Passenger Car With and Without Particle Filter - Christoph Bisig; Sandro Steiner; Pierre Comte; Jan Czerwinski; Andreas Mayer; Alke Petri-Fink; Barbara Rothen-Rutishauser (Emission Control Science and Technology, 2015)

Soot Oxidation Kinetics of Different Ceria Nanoparticle Catalysts - Georgia Kastrinaki; Souzana Lorentzou; Athanasios G. Konstandopoulos (Emission Control Science and Technology, 2015)

Impact of Combination of EGR, SCR, and DPF Technologies for the Low-Emission Rail Diesel Engines - Athanasios G. Konstandopoulos; Margaritis Kostoglou; Carlo Beatrice; Gabriele Di Blasio; Abdurrahman Imren; Ingemar Denbratt (Emission Control Science and Technology, 2015)

Development and Investigation of Diesel Fuel Reformer for LNT Regeneration - Thomas Wittka; Volker Müller; Peter Dittmann; Stefan Pischinger (Emission Control Science and Technology, 2015)

Emission Reduction with Diesel Particle Filter with SCR Coating (SDPF) - Jan Czerwinski; Yan Zimmerli; Andreas Mayer; Giovani D’Urbano; Daniel Zürcher (Emission Control Science and Technology, 2015)

Development of a Catalyzed Diesel Particulate Filter Multi-zone Model for Simulation of Axial and Radial Substrate Temperature and Particulate Matter Distribution - Boopathi S. Mahadevan; John H. Johnson; Mahdi Shahbakhti (Emission Control Science and Technology, 2015)

Diesel Engine SCR Control: Current Development and Future Challenges - Xinmei Yuan; Hongqi Liu; Ying Gao (Emission Control Science and Technology, 2015)

Interaction of NO x Reduction and Soot Oxidation in a DPF with Cu-Zeolite SCR Coating - E. Tronconi; I. Nova; F. Marchitti; G. Koltsakis; D. Karamitros; B. Maletic; N. Markert; D. Chatterjee; M. Hehle (Emission Control Science and Technology, 2015)

Recent Developments in the Measurement of Low Particulate Emissions from Mobile Sources: A Review of Particle Number Legislations - Oliver F. Bischof (Emission Control Science and Technology, 2015)

Experimental Investigation of Combined LNT + SCR Diesel Exhaust Aftertreatment - Thomas Wittka; Bastian Holderbaum; Peter Dittmann; Stefan Pischinger (Emission Control Science and Technology, 2015)

Oxidation of Soot (Printex® U) in Particulate Filters Operated on Gasoline Engines - Thorsten Boger; Dominik Rose; Per Nicolin; N. Gunasekaran; Thomas Glasson (Emission Control Science and Technology, 2015)

An Asymptotic Solution for Washcoat Pore Diffusion in Catalytic Monoliths - Edward J. Bissett (Emission Control Science and Technology, 2015)

Progression of Soot Cake Layer Properties During the Systematic Regeneration of Diesel Particulate Filters Measured with Neutron Tomography - Todd J. Toops; Josh A. Pihl; Charles E. A. Finney; Jens Gregor; Hassina Bilheux (Emission Control Science and Technology, 2015)

Isabella Nova, Enrico Tronconi: Urea-SCR Technology for deNOx Aftertreatment of Diesel Exhausts - Mansour Masoudi (Emission Control Science and Technology, 2015)

Modeling Urea-Water Solution Droplet Evaporation - Douglas T. Ryddner; Mario F. Trujillo (Emission Control Science and Technology, 2015)